Optical laminate and method for manufacturing same
By adopting a laminated body structure in the elliptical polarizer, and using a specific combination of a transparent protective film, an adhesive layer, a polarizer, an optical anisotropic layer and an adhesive layer, the problem of insufficient bending ability of the existing polarizer is solved, and an optical laminated body with high bending ability and durability is realized.
Patent Information
- Application Number
- CN202380059947.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-19
- Filing Date
- 2023-06-09
- Publication Date
- 2025-03-28
AI Technical Summary
The existing elliptical polarizers have insufficient bending properties and are difficult to meet the needs of flexible displays.
An optical laminate consisting of a transparent protective film, an adhesive layer, a polarizer, another adhesive layer, an optical anisotropic layer and an adhesive layer are used to improve the bending of the laminate by optimizing the thickness and material of the adhesive layer and the optical anisotropic layer.
The excellent bending of the optical laminate is achieved, and the problem of peeling or cracking occurs during repeated bending is avoided, and the performance of the flexible display is improved.
Smart Images

Figure CN119731565A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an optical layered body and a method for producing the same. Background Art
[0002] An elliptically polarizing plate is an optical component formed by laminating a polarizing plate and a phase difference plate, and is used, for example, in an image display device such as an organic EL image display device to prevent light reflection at an electrode constituting the device. As a phase difference plate, a phase difference plate using a liquid crystal cured film prepared by coating a polymerizable liquid crystal compound on a substrate and curing it is known (Patent Document 1).
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2022-044293 Summary of the invention
[0006] Problems to be solved by the invention
[0007] In recent years, with the popularization of bendable flexible displays, further bendability is required for elliptically polarizing plates. An object of the present invention is to provide an optical laminate having excellent bendability.
[0008] Means for solving problems
[0009] The present invention provides the following optical layered body and a method for producing the same.
[0010] [1] An optical laminate comprising, in order, a transparent protective film, a first adhesive layer, a polarizer, a second adhesive layer, an optically anisotropic layer, and a pressure-sensitive adhesive layer,
[0011] Only the first adhesive layer is sandwiched between the transparent protective film and the polarizer, and only the second adhesive layer is sandwiched between the polarizer and the optically anisotropic layer.
[0012] The optically anisotropic layer is a liquid crystal cured film.
[0013] The optically anisotropic layer has a thickness of 0.1 μm to 5 μm.
[0014] The optically anisotropic layer is directly in contact with the pressure-sensitive adhesive layer, or an orientation layer is included between the optically anisotropic layer and the pressure-sensitive adhesive layer.
[0015] [2] The optical layered body according to [1], wherein the thickness of the first adhesive layer and the second adhesive layer is 50 nm to 2000 nm.
[0016] [3] The optical layered body according to [1] or [2], wherein the first adhesive layer and the second adhesive layer are layers formed of a dry-curable adhesive or an active energy ray-curable adhesive.
[0017] [4] The optical layered body according to any one of [1] to [3], wherein the optically anisotropic layer has reverse wavelength dispersion.
[0018] [5] The optical layered body according to any one of [1] to [4], wherein the in-plane retardation value of the optically anisotropic layer with respect to light of a wavelength of 550 nm is 100 nm to 160 nm.
[0019] [6] The optical layered body according to any one of [1] to [5], wherein the optically anisotropic layer has an optical axis that is tilted with respect to the longitudinal direction of the polarizer.
[0020] [7] The optical laminate according to any one of [1] to [6], wherein the alignment layer is a photo-alignment film formed of a photo-alignment polymer containing a photoreactive group.
[0021] [8] The optical layered body according to any one of [1] to [7], further comprising an antireflection layer on the side of the transparent protective film opposite to the polarizer.
[0022] [9] The optical layered body according to any one of [1] to [8], wherein the polarizer is composed of a polyvinyl alcohol-based resin film containing a dichroic dye.
[0023]
[10] An image display device comprising the optical layered body according to any one of [1] to [9].
[0024]
[11] The method for producing an optical layered body according to any one of [1] to [9], comprising the following steps:
[0025] a retardation film preparation step of preparing a retardation film including an optical anisotropic layer, an orientation layer and a substrate film in sequence;
[0026] A first laminating step of laminating the transparent protective film and the polarizer using a first adhesive;
[0027] A second laminating step of laminating the polarizer and the optically anisotropic layer of the retardation film using a second adhesive;
[0028] a peeling step of peeling and removing the substrate film, or the substrate film and the alignment layer, from the laminate obtained in the second lamination step; and
[0029] The adhesive layer laminating step is to laminate the adhesive layer on the surface exposed by the peeling step.
[0030]
[12] The method for producing an optical layered body according to
[11] , wherein the first adhesive and the second adhesive are active energy ray-curable adhesives.
[0031]
[13] The method for manufacturing an optical layered body as described in
[12] further includes the following step: after the aforementioned second bonding step and before the aforementioned peeling step, irradiating the aforementioned phase difference film side of the layered body obtained by the aforementioned second bonding step with active energy rays to cure the aforementioned first adhesive and the aforementioned second adhesive.
[0032] Effects of the Invention
[0033] An optical layered body having excellent bendability can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] [ Figure 1 ] is a schematic cross-sectional view showing an example of the layer structure of an optical layered body.
[0035] [ Figure 2 ] is a schematic cross-sectional view showing another example of the layer structure of an optical layered body. DETAILED DESCRIPTION
[0036] Hereinafter, the embodiments of the present invention will be described with reference to the accompanying drawings, but the present invention is not limited to the following embodiments. All the following drawings are shown to help understand the present invention, and the size and shape of each component shown in the drawings are not necessarily consistent with the size and shape of the actual component.
[0037] <Optical laminate>
[0038] (1) Configuration of optical laminate
[0039] Figure 1 and Figure 2 It is a schematic cross-sectional view showing an example of the layer structure of the optical layered body (hereinafter, also simply referred to as “optical layered body”) according to the present invention.
[0040] Figure 1The optical laminate 1 shown includes a transparent protective film 10, a first adhesive layer 51, a polarizer 20, a second adhesive layer 52, an optically anisotropic layer (phase difference layer) 30, and an adhesive layer 40 in order. The transparent protective film 10 and the polarizer 20 are laminated via the first adhesive layer 51. The polarizer 20 and the optically anisotropic layer 30 are laminated via the second adhesive layer 52. Only the first adhesive layer 51 is sandwiched between the transparent protective film 10 and the polarizer 20. Only the second adhesive layer 52 is sandwiched between the polarizer 20 and the optically anisotropic layer 30. The optical laminate 1 includes an orientation layer 60 between the optically anisotropic layer 30 and the adhesive layer 40. In the optical laminate 1 , the first adhesive layer 51 is in direct contact with the transparent protective film 10 and the polarizer 20 , the second adhesive layer 52 is in direct contact with the polarizer 20 and the optically anisotropic layer 30 , and the alignment layer 60 is in direct contact with the optically anisotropic layer 30 and the pressure-sensitive adhesive layer 40 .
[0041] Figure 2 The optical laminate 2 shown does not have an orientation layer 60, but has Figure 1 The optical layered body 1 shown has the same layer structure. In the optical layered body 2, the optically anisotropic layer 30 and the pressure-sensitive adhesive layer 40 are directly in contact with each other.
[0042] like Figure 1 and Figure 2 As shown in the example, in the optical laminate, there is no substrate film (usually a thermoplastic resin film) between the polarizer 20 and the optical anisotropic layer 30 as a substrate used when forming the optical anisotropic layer 30, and an adhesive layer (the first adhesive layer 51) is used in the bonding of the transparent protective film 10 and the polarizer 20, and an adhesive layer (the second adhesive layer 52) is used in the bonding of the polarizer 20 and the optical anisotropic layer 30. Since the optical laminate according to the present invention has such a structure, it is excellent in bending, and even if it is repeatedly bent, it is not easy to produce undesirable conditions such as peeling and cracking in the bent portion. From the viewpoint of further improving the bending property, when the optical laminate has an orientation layer 60, it is preferred that only the orientation layer 60 is sandwiched between the optical anisotropic layer 30 and the adhesive layer 40.
[0043] The optical laminate may include other layers (for example, other layers with various functions that can be assembled in an image display device, etc.) in addition to the transparent protective film 10, the first adhesive layer 51, the polarizer 20, the second adhesive layer 52, the optical anisotropic layer 30, the orientation layer 60, and the adhesive layer 40. From the viewpoint of improving the bending property of the optical laminate, the other layers are not arranged between the transparent protective film 10 and the polarizer 20, and between the polarizer 20 and the optical anisotropic layer 30, and preferably between the optical anisotropic layer 30 and the adhesive layer 40.
[0044] The optical laminate can be suitably used as, for example, an elliptically polarizing plate. The term "elliptically polarizing plate" includes a circularly polarizing plate.
[0045] Hereinafter, elements constituting or capable of constituting the optical layered body will be described in detail.
[0046] (2) Transparent protective film
[0047] The optical laminate includes a transparent protective film 10 laminated on the side of the polarizer 20 opposite to the optical anisotropic layer 30. The polarizer 20 is thin and its surface is easily damaged. Therefore, in general, in order to prevent damage and contamination from the outside, protective films are often provided on both sides of the polarizer 20. However, in the optical laminate of the present invention, no transparent protective film is laminated on the surface of the polarizer 20 on the optical anisotropic layer 30 side. As a result, a thinner optical laminate with a low oblique reflectivity can be formed.
[0048] The transparent protective film 10 has a total light transmittance of preferably 90% or more, more preferably 92% or more. If the total light transmittance is above the above lower limit, an optical laminate having high transparency and excellent optical properties can be formed. The upper limit of the total light transmittance of the transparent protective film 10 is not particularly limited, and it can be 100% or less. The total light transmittance can be measured, for example, according to JIS K 7361.
[0049] The transmittance of the transparent protective film 10 at a wavelength of 380nm is preferably 30% or less, more preferably 25% or less, and further preferably 20% or less. If the transmittance is below the above upper limit, when the optical laminate comprising the transparent protective film 10 is assembled into an image display device, the internal layers (polarizer 20, optical anisotropic layer 30, etc.) constituting the optical laminate can be protected from the influence of ultraviolet rays exposed on the viewing side. The lower limit of the transmittance of the transparent protective film 10 at a wavelength of 380nm is not particularly limited and may also be 0%. In order to make the transmittance of the transparent protective film 10 at a wavelength of 380nm less than 30%, the transparent protective film 10 may also include an ultraviolet absorber, etc. The transmittance at a wavelength of 380nm can be measured, for example, according to a spectrophotometer.
[0050] As the transparent protective film 10, a thermoplastic resin film can be used. As thermoplastic resins that can constitute the transparent protective film, for example, cellulose resins such as cellulose triacetate; polyester resins such as polyethylene terephthalate and polyethylene naphthalate; polyethersulfone resins; polysulfone resins; polycarbonate resins; polyamide resins such as nylon and aromatic polyamide; polyimide resins; polyolefin resins such as polyethylene, polypropylene, and ethylene-propylene copolymers; cyclic polyolefin resins having a ring system and a norbornene structure (also referred to as norbornene-based resins); (meth) acrylic resins; polyarylate resins; polystyrene resins; polyvinyl alcohol resins, and mixtures thereof. It should be noted that in this specification, the so-called "(meth) propylene-" means that it can be either "propylene-" or "methpropylene-". "(Meth)" of (meth) acrylate, (meth) acryl, etc. also has the same meaning. Such resins can be made into a film by known means such as solvent casting method and melt extrusion method. The surface of the transparent protective film may be subjected to a surface treatment such as a mold release treatment such as a silicone treatment, a corona treatment, or a plasma treatment.
[0051] The transparent protective film 10 is preferably a cellulose triacetate film, a (meth)acrylic resin film, a cyclic polyolefin resin film, or a polyethylene terephthalate film.
[0052] In one embodiment, the transparent protective film 10 has a thickness of preferably 100 g / m 2 / 24 hours or more, more preferably 150g / m 2 / 24 hours or more, more preferably 200g / m 2 / 24 hours or more of moisture permeability. If the moisture permeability of the transparent protective film 10 is above the above lower limit, when the optical anisotropic layer 30 and the polarizer 20 are laminated using a dry curing adhesive to form an optical laminate, the solvent in the dry curing adhesive can be efficiently removed from the transparent protective film 10. As a result, the time for removing the solvent in the dry curing adhesive can be shortened, which is advantageous in terms of productivity. The upper limit of the moisture permeability of the transparent protective film 10 is not particularly limited, and is generally 1000 g / m 2 / 24 hours or less, preferably 500g / m 2 The moisture permeability is the moisture permeability at a temperature of 40°C and a relative humidity of 90%, and can be measured by the cup method specified in JIS Z 0208.
[0053] From the viewpoint of thinning, processability, bendability, strength, etc. of the optical laminate, the thickness of the transparent protective film 10 is usually 5 μm to 300 μm, preferably 20 μm to 200 μm, and more preferably 20 μm to 150 μm.
[0054] The transparent protective film 10 may include a surface treatment layer laminated on the surface opposite to the polarizer 20. As the surface treatment layer, for example, a hard coating layer, an anti-reflection layer, etc. can be cited. The hard coating layer is a layer for the purpose of preventing surface scratches, etc., and for example, a cured film obtained from a UV-curable resin such as a (meth) acrylic acid system and a silicone system can be cited. The anti-reflection layer is a layer for the purpose of preventing reflection of external light on the surface, and can be a conventionally known anti-reflection film, etc.
[0055] (3) Polarizer
[0056] The polarizer is a film having the function of extracting linear polarized light from incident natural light, and is preferably a polyvinyl alcohol resin film containing a dichroic pigment. As the polyvinyl alcohol resin constituting the polyvinyl alcohol resin film, a saponified product of a polyvinyl acetate resin can be used. As the polyvinyl acetate resin, in addition to polyvinyl acetate which is a homopolymer of vinyl acetate, copolymers of vinyl acetate and other monomers copolymerizable therewith (for example, ethylene-vinyl acetate copolymers, etc.) can also be cited. As other monomers copolymerizable with vinyl acetate, for example, unsaturated carboxylic acids, olefins, vinyl ethers, unsaturated sulfonic acids, (meth) acrylamides having an ammonium group, etc. can be cited.
[0057] The saponification degree of the polyvinyl alcohol resin is usually 85 mol% to 100 mol%, preferably 98 mol% or more. The polyvinyl alcohol resin may be modified, for example, polyvinyl formal and polyvinyl acetal modified with aldehydes may be used. The polymerization degree of the polyvinyl alcohol resin is usually 1,000 to 10,000, preferably 1,500 to 5,000.
[0058] The film obtained by forming the polyvinyl alcohol resin can be used as a raw film of a polarizer. The method of forming the polyvinyl alcohol resin is not particularly limited, and the film can be formed by a known method. The thickness of the polyvinyl alcohol raw film can be set to, for example, 10 μm to 150 μm.
[0059] Polarizers are usually manufactured through the following steps: a step of uniaxially stretching the polyvinyl alcohol resin film; a step of dyeing the polyvinyl alcohol resin film with a dichroic pigment to adsorb the dichroic pigment; a step of treating the polyvinyl alcohol resin film adsorbed with the dichroic pigment with a boric acid aqueous solution; and a step of washing the polyvinyl alcohol resin film with water after the treatment with the boric acid aqueous solution. It should be noted that the dichroic pigment is contained in the polyvinyl alcohol resin film by dyeing the polyvinyl alcohol resin film with a dichroic pigment. When the polarizer is manufactured using the above manufacturing method, the polarizer becomes a stretched polyvinyl alcohol resin film containing the dichroic pigment.
[0060] The uniaxial stretching of the polyvinyl alcohol resin film can be carried out before dyeing of the dichroic pigment, can be carried out simultaneously with dyeing, or can be carried out after dyeing. In the case of uniaxial stretching after dyeing, the uniaxial stretching can be carried out before boric acid treatment or during boric acid treatment. It is also possible to carry out uniaxial stretching in the above-mentioned multiple stages. During uniaxial stretching, it is possible to stretch uniaxially between rollers with different circumferential speeds, or to stretch uniaxially using a hot roller. In addition, the uniaxial stretching can be a dry stretching in which the film is stretched in the atmosphere, or it can be a wet stretching in which the film is stretched using a solvent while the polyvinyl alcohol resin film is swollen. From the viewpoint of suppressing the deformation of the polarizer, the stretching ratio is preferably 8 times or less, more preferably 7.5 times or less, and further preferably 7 times or less. In addition, from the viewpoint of presenting the function as a polarizer, the stretching ratio is generally 4.5 times or more. By making the stretching ratio within the aforementioned range, the time-dependent deformation of the polarizer can be suppressed.
[0061] As a method for utilizing dichroic pigment to dye the polyvinyl alcohol resin film, for example, a method for immersing the polyvinyl alcohol resin film in an aqueous solution containing dichroic pigment can be enumerated. As dichroic pigment, for example, iodine or dichroic dye can be used. Dichroic dye includes dichroic direct dyes formed by disazo compounds such as CI Direct Red (DIRECT RED) 39, dichroic direct dyes formed by triazo, tetrazo compounds, etc. It should be noted that the polyvinyl alcohol resin film is preferably implemented in advance in the immersion treatment in water before the dyeing treatment.
[0062] When iodine is used as a dichroic pigment, a method of dyeing is usually performed by immersing a polyvinyl alcohol-based resin film in an aqueous solution containing iodine and potassium iodide. The content of iodine in the aqueous solution is usually 0.01 mass parts or more and 1 mass parts or less per 100 mass parts of water. In addition, the content of potassium iodide is usually 0.5 mass parts or more and 20 mass parts or less per 100 mass parts of water. The temperature of the aqueous solution used in dyeing is usually 20°C or more and 40°C or less. In addition, the immersion time (dyeing time) in the aqueous solution is usually 20 seconds or more and 1,800 seconds or less.
[0063] It should be noted that before immersing the polyvinyl alcohol-based resin film in an aqueous solution containing iodine and potassium iodide, the film may be immersed in water in order to swell the film and facilitate dyeing. The immersion treatment temperature is usually 20° C. to 80° C., preferably 30° C. to 60° C., and the immersion time (dyeing time) is usually 20 seconds to 1,800 seconds.
[0064] On the other hand, when a dichroic organic dye is used as a dichroic pigment, a method of dyeing the polyvinyl alcohol-based resin film by immersing it in an aqueous solution containing a water-soluble dichroic dye is generally adopted. The content of the dichroic organic dye in the aqueous solution is generally 1×10 -4 mass parts or more and about 10 mass parts or less, preferably 1×10 -3 1 part by mass or more and 1 part by mass or less, more preferably 1×10 -3 Mass parts or more 1×10 -2 The aqueous solution may contain an inorganic salt such as sodium sulfate as a dyeing auxiliary. The temperature of the dichroic dye aqueous solution used in dyeing is usually 20°C or more and about 80°C or less. In addition, the immersion time (dyeing time) in the aqueous solution is usually 10 seconds or more and about 1,800 seconds or less.
[0065] Boric acid treatment after dyeing based on dichroic pigments can usually be carried out by immersing the dyed polyvinyl alcohol-based resin film in an aqueous solution of boric acid. The content of boric acid in the aqueous solution of boric acid is usually 2 parts by mass or more and about 15 parts by mass or less per 100 parts by mass of water, preferably 5 parts by mass or more and about 12 parts by mass or less. In the case of using iodine as a dichroic pigment, the aqueous solution of boric acid preferably contains potassium iodide, in which case the content of potassium iodide is usually 0.1 parts by mass or more and about 15 parts by mass or less per 100 parts by mass of water, preferably 5 parts by mass or more and about 12 parts by mass or less. The immersion time in the aqueous solution of boric acid is usually 60 seconds or more and about 1,200 seconds or less, preferably 150 seconds or more and 600 seconds or less, and more preferably 200 seconds or more and 400 seconds or less. The temperature of the boric acid treatment is usually 50°C or more, preferably 50°C or more and 85°C or less, and more preferably 60°C or more and 80°C or less.
[0066] The polyvinyl alcohol-based resin film after the boric acid treatment is usually subjected to a water washing treatment. The water washing treatment can be performed, for example, by immersing the polyvinyl alcohol-based resin film treated with boric acid in water. The temperature of the water in the water washing treatment is usually 5° C. to about 40° C. or less. In addition, the immersion time is usually 1 second to about 120 seconds or less.
[0067] After washing, drying treatment is performed to obtain a polarizer 20. The drying treatment can be performed using, for example, a hot air dryer or a far-infrared heater. The temperature of the drying treatment is usually between about 30°C and about 100°C, preferably between about 50°C and about 80°C. The time of the drying treatment is usually between about 60 seconds and about 600 seconds, preferably between about 120 seconds and about 600 seconds. By drying treatment, the moisture content of the polarizer is reduced to a practical level. Its moisture content is usually between about 5% by mass and about 20% by mass, preferably between about 8% by mass and about 15% by mass. If the moisture content is within the above range, it is easy to obtain a polarizer with moderate flexibility and excellent thermal stability.
[0068] The thickness of the polarizer 20 is preferably 5 μm to 40 μm, and more preferably 5 μm to 20 μm.
[0069] (4) Optically anisotropic layer and oriented layer
[0070] The optically anisotropic layer 30 is formed by coating a composition containing a polymerizable liquid crystal compound (hereinafter, also referred to as a "liquid crystal cured film forming composition") on a transparent substrate, and is formed by a polymer in which the polymerizable liquid crystal compound is oriented (hereinafter, also referred to as a "liquid crystal cured film"). Since the optically anisotropic layer 30 is a liquid crystal cured film, it can be thinned and the wavelength dispersion characteristics can be arbitrarily designed. In addition, the liquid crystal cured film forming composition may further include a solvent, a photopolymerization initiator, a photosensitizer, an inhibitor, a leveling agent, and an adhesion improver.
[0071] The liquid crystal cured film is usually formed by applying a composition for forming a liquid crystal cured film on an orientation layer formed on a substrate, and polymerizing the polymerizable liquid crystal compound contained in the composition for forming a liquid crystal cured film. The liquid crystal cured film is usually a film obtained by curing the polymerizable liquid crystal compound in an oriented state. In order to produce a phase difference in the viewing surface, it must be a cured film obtained by polymerizing the polymerizable group in a state where the polymerizable liquid crystal compound is oriented in a direction parallel to the substrate surface. At this time, if the polymerizable liquid crystal compound is a rod-shaped liquid crystal, a positive A plate can be used, and if the polymerizable liquid crystal compound is a disc-shaped liquid crystal, a negative A plate can be used.
[0072] The liquid crystal curing film may be a λ / 4 layer, a λ / 2 layer or a positive C layer. The optically anisotropic layer 30 may include more than two layers of liquid crystal curing film. As a combination of more than two layers of liquid crystal curing films, for example, a combination of a λ / 4 layer and a λ / 2 layer, a combination of a λ / 4 layer and a positive C layer, etc. may be cited. From the perspective of highly achieving an anti-reflection function, it is sufficient to have a λ / 4 plate function (i.e., a phase difference function of π / 2) in the entire visible light domain. Specifically, it is preferably a reverse wavelength dispersion λ / 4 layer, or it may be a film obtained by combining a positive wavelength dispersion λ / 2 layer with a positive wavelength dispersion λ / 4 layer. In addition, from the perspective of being able to compensate for the function of preventing reflection in an oblique direction, it is preferred to further include a layer having anisotropy in the thickness direction (positive C plate). In addition, each optically anisotropic layer may be tiltedly oriented or may form a cholesteric orientation state. In the case where the optically anisotropic layer 30 includes more than two layers of liquid crystal curing films, the optically anisotropic layer 30 may include a bonding layer (adhesive layer or adhesive layer) for bonding these liquid crystal curing films to each other.
[0073] The optically anisotropic layer 30 preferably has an in-plane retardation value Re(λ) for light of wavelength λ nm that satisfies the following formula (1), and more preferably further satisfies the following formula (1), the following formula (2), and the following formula (3).
[0074] 100nm≤Re(550)≤160nm · · · (1)
[0075] (Wherein, Re(550) represents the in-plane phase difference value (in-plane retardation) for light with a wavelength of 550 nm.)
[0076] Re(450) / Re(550)≤1.0 · · · (2)
[0077] 1.00≤Re(650) / Re(550) · · (3)
[0078] (Wherein, Re(450) represents the in-plane phase difference value for light with a wavelength of 450 nm, Re(550) represents the in-plane phase difference value for light with a wavelength of 550 nm, and Re(650) represents the in-plane phase difference value for light with a wavelength of 650 nm.)
[0079] When the optical anisotropic layer 30 satisfies the formula (1), it is easy to improve the front reflection hue during black display when the optical laminate (elliptically polarizing plate) including the optical anisotropic layer 30 is applied to an image display device such as an organic EL display device. The Re (550) of the optical anisotropic layer 30 is more preferably 130 nm or more and 150 nm or less.
[0080] The optically anisotropic layer 30 preferably has reverse wavelength dispersion, and specifically, preferably satisfies formula (2) and formula (3). If the value of "Re(450) / Re(550)" of the optically anisotropic layer 30 is greater than 1.0, the light leakage on the short wavelength side of the elliptically polarizing plate having the optically anisotropic layer increases. The value of "Re(450) / Re(550)" is preferably 0.7 to 1.0, more preferably 0.80 to 0.95, further preferably 0.80 to 0.92, and particularly preferably 0.82 to 0.88. The value of "Re(450) / Re(550)" can be arbitrarily adjusted by adjusting the mixing ratio of the polymerizable liquid crystal compound, the stacking angle of multiple liquid crystal cured films, and the phase difference value.
[0081] The in-plane phase difference value Re(λ) of the optical anisotropic layer 30 can be adjusted by the thickness of the optical anisotropic layer 30. The in-plane phase difference value Re(λ) is determined by the following formula (4). Therefore, in order to obtain the desired in-plane phase difference value Re(λ), it is sufficient to adjust Δn(λ) and the film thickness d. The thickness of the optical anisotropic layer 30 can be measured using an interference film thickness meter, a laser microscope or a stylus film thickness meter. It should be noted that Δn(λ) depends on the molecular structure of the polymerizable liquid crystal compound described later.
[0082] Re(λ)=d×Δn(λ) · · · (4)
[0083] (Where Re(λ) represents the in-plane phase difference at a wavelength of λnm, d represents the film thickness, and Δn(λ) represents the birefringence at a wavelength of λnm.)
[0084] In addition, the phase difference value Rth(550) in the thickness direction at a wavelength of 550nm of the positive C layer is usually in the range of -170nm to -10nm, preferably in the range of -150nm to -20nm, and more preferably in the range of -100nm to -40nm. If the phase difference value in the thickness direction is within this range, the characteristic of preventing reflection from an oblique direction can be further improved.
[0085] The so-called polymerizable liquid crystal compound refers to a liquid crystal compound having a polymerizable group, especially a photopolymerizable group. As the polymerizable liquid crystal compound, for example, a polymerizable liquid crystal compound previously known in the field of phase difference film can be used. The so-called photopolymerizable group refers to a group that can participate in the polymerization reaction using reactive species, such as active free radicals, acids, etc., generated by a photopolymerization initiator. As a photopolymerizable group, vinyl, vinyloxy, 1-chlorovinyl, isopropenyl, 4-vinylphenyl, acryloyloxy, methacryloyloxy, oxypropyl, oxetane, etc. can be cited. Among them, acryloyloxy, methacryloyloxy, vinyloxy, oxypropyl and oxetane are preferred, and acryloyloxy is more preferred. Regarding liquid crystal, it can be a thermotropic liquid crystal or a lyotropic liquid crystal, but from the perspective of being able to perform precise film thickness control, it is preferably a thermotropic liquid crystal. In addition, as a phase-ordered structure in a thermotropic liquid crystal, it can be a nematic liquid crystal or a smectic liquid crystal. In addition, it can be a rod-shaped liquid crystal or a disc-shaped liquid crystal. The polymerizable liquid crystal compounds may be used alone or in combination of two or more.
[0086] As a polymerizable liquid crystal compound, from the viewpoint of exhibiting reverse wavelength dispersion, it is preferred to be a liquid crystal having a T-type or H-type mesomorphic structure which further has birefringence in a direction perpendicular to the long axis direction of the molecule. From the viewpoint of obtaining stronger dispersion, a T-type liquid crystal is more preferred. Specifically, as the structure of the T-type liquid crystal, for example, a compound represented by the following formula (I) can be cited.
[0087] [Chemical formula 1]
[0088]
[0089] In formula (I), Ar represents a divalent aromatic group which may have a substituent. Preferably, the divalent aromatic group contains at least one of a nitrogen atom, an oxygen atom, and a sulfur atom. When the number of aromatic groups contained in the divalent group Ar is two or more, the two or more aromatic groups may be bonded to each other through a divalent bonding group such as a single bond, -CO-O-, or -O-.
[0090] G 1 and G 2 Each independently represents a divalent aromatic group or a divalent alicyclic hydrocarbon group. Here, the hydrogen atoms contained in the divalent aromatic group or the divalent alicyclic hydrocarbon group may be substituted by a halogen atom, an alkyl group having 1 to 4 carbon atoms, a fluoroalkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a cyano group or a nitro group, and the carbon atoms constituting the divalent aromatic group or the divalent alicyclic hydrocarbon group may be replaced by an oxygen atom, a sulfur atom or a nitrogen atom.
[0091] L 1 , L2 , B 1 and B 2 Each is independently a single bond or a divalent linking group.
[0092] k and l each independently represent an integer of 0 to 3 and satisfy the relationship 1≤k+1. Here, when 2≤k+1, B 1 and B 2 , G 1 and G 2 Each may be the same as or different from each other.
[0093] E 1 and E 2 Each independently represents an alkanediyl group having 1 to 17 carbon atoms, wherein the hydrogen atoms contained in the alkanediyl group may be substituted by halogen atoms, and the -CH2- contained in the alkanediyl group may be replaced by -O-, -S-, or -COO-. When there are multiple -O-, -S-, or -COO-, they are not adjacent to each other. 1 and P 2 Each independently represents a polymerizable group or a hydrogen atom, and at least one of them is a polymerizable group.
[0094] G 1 and G 2 Each independently preferably is a 1,4-phenylenediyl group which may be substituted with at least one substituent selected from the group consisting of a halogen atom and an alkyl group having 1 to 4 carbon atoms, or a 1,4-cyclohexanediyl group which may be substituted with at least one substituent selected from the group consisting of a halogen atom and an alkyl group having 1 to 4 carbon atoms; more preferably is a 1,4-phenylenediyl group substituted with a methyl group, an unsubstituted 1,4-phenylenediyl group, or an unsubstituted 1,4-trans-cyclohexanediyl group; and particularly preferably is an unsubstituted 1,4-phenylenediyl group or an unsubstituted 1,4-trans-cyclohexanediyl group.
[0095] In addition, it is preferred that there are multiple G 1 and G 2 At least one of them is a divalent alicyclic hydrocarbon group, and more preferably 1 or L 2 Bonded G 1 and G 2 At least one of them is a divalent alicyclic hydrocarbon group.
[0096] L 1 and L 2 Each of them is independently preferably a single bond, an alkylene group having 1 to 4 carbon atoms, -O-, -S-, -R a1 OR a2 -、-R a3 COOR a4 -、-R a5 OCORa6 -、R a7 OC=OOR a8 -、-N=N-、-CR c =CR d -, or -C≡C-. Here, R a1 ~R a8 Each independently represents a single bond or an alkylene group having 1 to 4 carbon atoms, and R c and R d represents an alkyl group having 1 to 4 carbon atoms or a hydrogen atom. 1 and L 2 Each independently is more preferably a single bond, -OR a2-1 -、-CH2-、-CH2CH2-、-COOR a4-1 -, or -OCOR a6-1 -. Here, R a2-1 , R a4-1 , R a6-1 Each independently represents a single bond, -CH2-, or -CH2CH2-. 1 and L 2 Each independently is further preferably a single bond, -O-, -CH2CH2-, -COO-, -COOCH2CH2-, or -OCO-.
[0097] B 1 and B 2 Each of them is independently preferably a single bond, an alkylene group having 1 to 4 carbon atoms, -O-, -S-, -R a9 OR a10 -、-R a11 COOR a12 -、-R a13 OCOR a14 -, or -R a15 OC=OOR a16 -. Here, R a9 ~R a16 Each independently represents a single bond or an alkylene group having 1 to 4 carbon atoms. 1 and B 2 Each independently is more preferably a single bond, -OR a10-1 -、-CH2-、-CH2CH2-、-COOR a12 -1 -, or -OCOR a14-1 -. Here, R a10-1 , R a12-1 , R a14-1 Each independently represents a single bond, -CH2-, or -CH2CH2-. 1 and B 2Each independently is further preferably a single bond, -O-, -CH2CH2-, -COO-, -COOCH2CH2-, -OCO-, or -OCOCH2CH2-.
[0098] From the viewpoint of exhibiting reverse wavelength dispersion, k and l preferably satisfy 2≤k+l≤6, more preferably k+l=4, and still more preferably k=2 and l=2. k=2 and l=2 are preferred because a symmetrical structure is obtained.
[0099] E 1 and E 2 Each independently is preferably an alkanediyl group having 1 to 17 carbon atoms, and more preferably an alkanediyl group having 4 to 12 carbon atoms.
[0100] As P 1 or P 2 The polymerizable group represented by , includes epoxy, vinyl, vinyloxy, 1-chlorovinyl, isopropenyl, 4-vinylphenyl, acryloyloxy, methacryloyloxy, oxirane and oxetanyl, etc. Among them, acryloyloxy, methacryloyloxy, vinyloxy, oxirane and oxetanyl are preferred, and acryloyloxy is more preferred.
[0101] Ar preferably has at least one selected from an aromatic hydrocarbon ring that may have a substituent, an aromatic heterocycle that may have a substituent, and an electron-withdrawing group. As the aromatic hydrocarbon ring, for example, a benzene ring, a naphthalene ring, an anthracene ring, etc. can be cited, preferably a benzene ring, a naphthalene ring. As the aromatic heterocycle, a furan ring, a benzofuran ring, a pyrrole ring, an indole ring, a thiophene ring, a benzothiophene ring, a pyridine ring, a pyrazine ring, a pyrimidine ring, a triazole ring, a triazine ring, a pyrroline ring, an imidazole ring, a pyrazole ring, a thiazole ring, a benzothiazole ring, a thienothiazole ring, an oxazole ring, a benzoxazole ring and a phenanthroline ring can be cited. Among them, preferably there is a thiazole ring, a benzothiazole ring or a benzofuran ring, and further preferably there is a benzothiazolyl group. In addition, when Ar contains a nitrogen atom, the nitrogen atom preferably has π electrons.
[0102] In formula (I), the total number Nπ of π electrons contained in the divalent aromatic group represented by Ar is usually 6 or more, preferably 8 or more, more preferably 10 or more, further preferably 14 or more, and particularly preferably 16 or more. In addition, the total number Nπ is preferably 30 or less, more preferably 26 or less, and further preferably 24 or less.
[0103] As the aromatic group represented by Ar, for example, the following groups are preferably mentioned.
[0104] [Chemical formula 2]
[0105]
[0106] In the formulas (Ar-1) to (Ar-23), the symbol * represents a connecting portion, and Z 0 , Z 1 and Z 2 Each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, a cyano group, a nitro group, an alkylsulfinyl group having 1 to 12 carbon atoms, an alkylsulfonyl group having 1 to 12 carbon atoms, a carboxyl group, a fluoroalkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, an alkylthio group having 1 to 12 carbon atoms, an N-alkylamino group having 1 to 12 carbon atoms, an N,N-dialkylamino group having 2 to 12 carbon atoms, an N-alkylsulfamoyl group having 1 to 12 carbon atoms, or an N,N-dialkylsulfamoyl group having 2 to 12 carbon atoms.
[0107] Q 1 , Q 2 and Q 3 Each independently represents -CR 2’ R 3’ -、-S-、-NH-、-NR 2’ -, -CO- or -O-, R 2’ and R 3’ Each independently represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.
[0108] J 1 and J 2 Each independently represents a carbon atom or a nitrogen atom.
[0109] Y 1 , Y 2 and Y 3 Each independently represents an aromatic hydrocarbon group or an aromatic heterocyclic group which may be substituted.
[0110] W 1 and W 2 Each independently represents a hydrogen atom, a cyano group, a methyl group or a halogen atom, and m represents an integer of 0-6.
[0111] As Y 1 , Y 2 and Y 3 The aromatic hydrocarbon group in the group includes an aromatic hydrocarbon group having 6 to 20 carbon atoms, such as phenyl, naphthyl, anthracenyl, phenanthrenyl, biphenyl, etc., preferably phenyl and naphthyl, more preferably phenyl. The aromatic heterocyclic group includes an aromatic heterocyclic group having 4 to 20 carbon atoms, such as furanyl, pyrrolyl, thienyl, pyridyl, thiazolyl, benzothiazolyl, etc., which contains at least one hetero atom such as nitrogen atom, oxygen atom, sulfur atom, etc., preferably furanyl, thienyl, pyridyl, thiazolyl, benzothiazolyl.
[0112] Y 1 , Y 2 and Y3 Each independently may be a substituted polycyclic aromatic hydrocarbon group or a polycyclic aromatic heterocyclic group. The polycyclic aromatic hydrocarbon group refers to a condensed polycyclic aromatic hydrocarbon group or a group derived from an aromatic ring collection. The polycyclic aromatic heterocyclic group refers to a condensed polycyclic aromatic heterocyclic group or a group derived from an aromatic ring collection.
[0113] Z 0 , Z 1 and Z 2 Each of Z is independently preferably a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, a cyano group, a nitro group, or an alkoxy group having 1 to 12 carbon atoms. 0 More preferably, a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a cyano group. 1 and Z 2 More preferred are a hydrogen atom, a fluorine atom, a chlorine atom, a methyl group and a cyano group.
[0114] Q 1 , Q 2 and Q 3 Preferred are -NH-, -S-, -NR 2’ -、-O-,R 2’ A hydrogen atom is preferred, and -S-, -O-, and -NH- are particularly preferred.
[0115] Among formulae (Ar-1) to (Ar-23), formulae (Ar-6) and (Ar-7) are preferred from the viewpoint of molecular stability.
[0116] In the formulas (Ar-16) to (Ar-23), Y 1 The nitrogen atom and Z to which it can be bonded 0 Together, they form an aromatic heterocyclic group. Examples of the aromatic heterocyclic group include the aromatic heterocyclic rings that Ar may have and are described above, for example, a pyrrole ring, an imidazole ring, a pyrroline ring, a pyridine ring, a pyrazine ring, a pyrimidine ring, an indole ring, a quinoline ring, an isoquinoline ring, a purine ring, a pyrrolidine ring, etc. The aromatic heterocyclic group may have a substituent. In addition, Y 1 It can also be bonded to the nitrogen atom and Z 0 Together, they form the aforementioned optionally substituted polycyclic aromatic hydrocarbon group or polycyclic aromatic heterocyclic group, for example, a benzofuran ring, a benzothiazole ring, a benzoxazole ring, and the like.
[0117] Among polymerizable liquid crystal compounds, compounds with a maximum absorption wavelength of more than 300nm and less than 400nm are preferred. In the case of including a photopolymerization initiator in a composition for forming a liquid crystal curable film, there is concern about the polymerization reaction and gelation of the polymerizable liquid crystal compound during long-term storage. However, when the maximum absorption wavelength of the polymerizable liquid crystal compound is more than 300nm and less than 400nm, even if it is exposed to ultraviolet light during storage, it is possible to effectively suppress the generation of reactive species from the photopolymerization initiator and the polymerization reaction and gelation of the polymerizable liquid crystal compound caused by the reactive species. Therefore, it is advantageous from the perspective of the long-term stability of the composition for forming a liquid crystal curable film, and the uniformity of the orientation and film thickness of the obtained liquid crystal curable film can be improved. It should be noted that the maximum absorption wavelength of the polymerizable liquid crystal compound can be measured in a solvent using an ultraviolet-visible spectrophotometer. The solvent is a solvent that can dissolve the polymerizable liquid crystal compound, and for example, chloroform can be cited.
[0118] Relative to 100 parts by mass of the solid content of the composition for forming a liquid crystal curable film, the content of the polymerizable liquid crystal compound in the composition for forming a liquid crystal curable film is, for example, 70 parts by mass or more and 99.5 parts by mass or less, preferably 80 parts by mass or more and 99 parts by mass or less, more preferably 85 parts by mass or more and 98 parts by mass or less, and further preferably 90 parts by mass or more and 95 parts by mass or less. When the content of the polymerizable liquid crystal compound is within the above range, it is advantageous from the perspective of the orientation of the obtained optically anisotropic layer. It should be noted that in this specification, the so-called solid content of the composition for forming a liquid crystal curable film refers to all components obtained by removing volatile components such as organic solvents from the composition for forming a liquid crystal curable film.
[0119] The composition for forming a liquid crystal cured film may contain, in addition to the polymerizable liquid crystal compound, additives such as a solvent, a polymerization initiator, a leveling agent, an antioxidant, a photosensitizer, a reactive additive, a vertical alignment promoter, and a polymerizable non-liquid crystal compound. Each of these components may be used alone or in combination of two or more.
[0120] The composition for forming a liquid crystal solidified film is usually applied to a substrate film, etc., in a state dissolved in a solvent, and therefore preferably contains a solvent. Generally, the viscosity of the polymerizable liquid crystal compound is high, and therefore, in most cases, coating is made easy by making a composition for forming a liquid crystal solidified film dissolved in a solvent, and as a result, it becomes easy to form an optical anisotropic layer. As a solvent, it is preferably a solvent that can completely dissolve the polymerizable liquid crystal compound, and in addition, it is preferably a solvent that is inactive for the polymerization reaction of the polymerizable liquid crystal compound. In addition, it is preferably a solvent that will not dissolve the substrate film used. Examples of the solvent include alcohol solvents such as water, methanol, ethanol, ethylene glycol, isopropanol, propylene glycol, ethylene glycol methyl ether, ethylene glycol butyl ether, 1-methoxy-2-propanol, 2-butoxyethanol, and propylene glycol monomethyl ether; ester solvents such as ethyl acetate, butyl acetate, ethylene glycol methyl ether acetate, γ-butyrolactone, propylene glycol methyl ether acetate, and ethyl lactate; ketone solvents such as acetone, methyl ethyl ketone, cyclopentanone, cyclohexanone, 2-heptanone, and methyl isobutyl ketone; aliphatic hydrocarbon solvents such as pentane, hexane, and heptane; alicyclic hydrocarbon solvents such as ethyl cyclohexane; aromatic hydrocarbon solvents such as toluene, xylene, and anisole; nitrile solvents such as acetonitrile; ether solvents such as tetrahydrofuran and dimethoxyethane; chlorinated solvents such as chloroform and chlorobenzene; amide solvents such as dimethylacetamide, dimethylformamide, N-methyl-2-pyrrolidone (NMP), and 1,3-dimethyl-2-imidazolidinone; and the like. These solvents can be used alone or in combination of two or more. Among them, from the viewpoint of film coating, it is preferred to use at least one selected from alcohol solvents, ester solvents, ketone solvents, chlorinated solvents, amide solvents and aromatic hydrocarbon solvents, and from the viewpoint of the solubility of polymerizable liquid crystal compounds, it is more preferred to use at least one selected from ester solvents, ketone solvents, amide solvents and aromatic hydrocarbon solvents.
[0121] Relative to 100 parts by mass of polymerizable liquid crystal composition, the content of the solvent in the composition for forming liquid crystal curing film is preferably 50 parts by mass or more and 98 parts by mass or less, more preferably 70 parts by mass or more and 95 parts by mass or less. Therefore, the solid component preferably accounts for 2 parts by mass or less and 50 parts by mass or less in 100 parts by mass of the composition for forming liquid crystal curing film, more preferably 5 to 30% by mass. If the solid component is 50 parts by mass or less, the viscosity of the composition for forming liquid crystal curing film decreases, so there is a tendency that the thickness of the film becomes roughly uniform and is not easy to produce unevenness. The above-mentioned solid component can be appropriately determined in consideration of the thickness of the liquid crystal curing film to be manufactured.
[0122] A polymerization initiator is a compound that can generate reactive species with the aid of heat or light and initiate a polymerization reaction of a polymerizable liquid crystal compound or the like. As reactive species, there can be mentioned active species such as free radicals, cations or anions. Among them, from the viewpoint of easy control of the reaction, a photopolymerization initiator that generates free radicals by light irradiation is preferred.
[0123] The photopolymerization initiator may be any compound capable of initiating a polymerization reaction of a polymerizable liquid crystal compound, and known photopolymerization initiators may be used. Specifically, photopolymerization initiators capable of generating active free radicals or acids by the action of light may be cited, and photopolymerization initiators capable of generating free radicals by the action of light are preferred. The photopolymerization initiators may be used alone or in combination of two or more.
[0124] As the photopolymerization initiator, a known photopolymerization initiator can be used. For example, as a photopolymerization initiator that generates active free radicals, self-cleaving benzoin compounds, acetophenone compounds, hydroxyacetophenone compounds, α-aminoacetophenone compounds, oxime ester compounds, acylphosphine oxide compounds, azo compounds, etc. can be used, and hydrogen-abstracting benzophenone compounds, alkylphenone compounds, benzoin ether compounds, benzyl ketal compounds, dibenzosuberone compounds, anthraquinone compounds, xanthone compounds, thioxanthone compounds, halogenated acetophenone compounds, dialkoxyacetophenone compounds, halogenated bisimidazole compounds, halogenated triazine compounds, triazine compounds, etc. can be used. As a photopolymerization initiator that generates an acid, iodonium salts and sulfonium salts can be used. From the viewpoint of excellent reaction efficiency at low temperatures, self-cleavage type photopolymerization initiators are preferred, and acetophenone compounds, hydroxyacetophenone compounds, α-aminoacetophenone compounds, and oxime ester compounds are particularly preferred.
[0125] The photopolymerization initiator contained in the liquid crystal cured film-forming composition may be at least one kind, or may be used in combination of two or more kinds, and may be appropriately selected according to the relationship with the polymerizable liquid crystal compound contained in the liquid crystal cured film-forming composition.
[0126] The content of the polymerization initiator in the composition for forming a liquid crystal cured film can be appropriately adjusted according to the type and amount of the polymerizable liquid crystal compound, and is generally 0.1 to 30 parts by mass, preferably 0.5 to 10 parts by mass, and more preferably 0.5 to 8 parts by mass, relative to 100 parts by mass of the content of the polymerizable liquid crystal compound. If the content of the polymerization initiator is within the above range, polymerization can be performed without disturbing the orientation of the polymerizable liquid crystal compound.
[0127] The leveling agent is an additive having the function of adjusting the fluidity of the composition for forming a liquid crystal cured film and making the coating obtained by applying the composition for forming a liquid crystal cured film flatter. For example, it is preferably a polymer component containing a fluorine atom or a silicon atom or a polyacrylate polymer, and more preferably a surfactant having a polymer component containing a fluorine atom or a silicon atom as a main component. Specifically, organic modified silicone oil-based, polyacrylate-based, and perfluoroalkyl-based leveling agents can be cited. Among them, polyacrylate-based leveling agents and perfluoroalkyl-based leveling agents are preferred.
[0128] The content of the leveling agent is preferably 0.01 to 5 parts by mass relative to 100 parts by mass of the polymerizable liquid crystal compound, more preferably 0.05 to 3 parts by mass, and further preferably 0.05 to 1 part by mass. If the content of the leveling agent is within the above range, there is a tendency to easily orient the polymerizable liquid crystal compound and to make the obtained optically anisotropic layer 30 smoother. If the content of the leveling agent relative to the polymerizable liquid crystal compound exceeds the above range, there is a tendency to easily produce unevenness in the obtained optically anisotropic layer 30. The composition for forming a liquid crystal cured film may contain two or more leveling agents.
[0129] By matching an antioxidant, the polymerization reaction of the polymerizable liquid crystal compound can be controlled. As an antioxidant, it can be a main antioxidant selected from phenolic antioxidants, amine antioxidants, quinone antioxidants and nitroso antioxidants, or it can be an auxiliary antioxidant selected from phosphorus antioxidants and sulfur antioxidants. In order to polymerize the polymerizable liquid crystal compound without disturbing the orientation of the polymerizable liquid crystal compound, the content of the antioxidant is generally 0.01 mass parts or more and 10 mass parts or less relative to 100 mass parts of the polymerizable liquid crystal compound, preferably 0.1 mass parts or more and 5 mass parts or less, more preferably 0.1 mass parts or more and 3 mass parts or less. Antioxidants can be used alone or in combination of two or more.
[0130] By using a photosensitizer, the photopolymerization initiator can be made highly sensitive. As the photosensitizer, for example, xanthone such as xanthone, thioxanthone; anthracene, anthracene having a substituent such as an alkyl ether; phenothiazine; rubrene. The photosensitizer can be used alone or in combination of two or more. The content of the photosensitizer is usually 0.01 to 10 parts by mass, preferably 0.05 to 5 parts by mass, and more preferably 0.1 to 3 parts by mass, relative to 100 parts by mass of the polymerizable liquid crystal compound.
[0131] The liquid crystal cured film-forming composition for forming a liquid crystal cured film can be obtained by stirring components such as a polymerizable liquid crystal compound, a solvent, and a polymerization initiator at a predetermined temperature.
[0132] The liquid crystal cured film can be produced, for example, by a method including the following steps:
[0133] A step of forming a coating film of a composition for forming a liquid crystal cured film containing at least one polymerizable liquid crystal compound on a substrate film or an alignment layer 60 described later, drying the coating film, and orienting the polymerizable liquid crystal compound in the composition for forming a liquid crystal cured film; and
[0134] A step of polymerizing a polymerizable liquid crystal compound while maintaining an aligned state to form a liquid crystal cured film.
[0135] The coating film of the composition for forming a liquid crystal cured film can be formed by applying the composition for forming a liquid crystal cured film on a substrate film or an alignment layer 60 formed on the substrate film. As a method for applying the composition for forming a liquid crystal cured film on a substrate film, etc., there can be mentioned known methods such as coating methods such as spin coating, extrusion, gravure coating, die coating, bar coating, and applicator method, and printing methods such as flexographic method.
[0136] As the substrate film, a glass substrate and a film substrate can be mentioned, preferably a film substrate, and from the perspective of being able to be continuously manufactured, a long roll film substrate is more preferred. As the resin constituting the film substrate, for example, polyolefins such as polyethylene, polypropylene, and norbornene polymers; cyclic olefin resins; polyvinyl alcohol; polyethylene terephthalate; polymethacrylate; polyacrylate; cellulose esters such as cellulose triacetate, cellulose diacetate, and cellulose acetate propionate; polyethylene naphthalate; polycarbonate; polysulfone; polyethersulfone; polyetherketone; polyphenylene sulfide and polyphenylene ether; and other plastics can be mentioned. Among them, from the perspective of transparency when used for optical film applications, a film substrate selected from any one of cellulose triacetate, cyclic olefin resins, polymethacrylate, and polyethylene terephthalate is more preferred.
[0137] From the viewpoint of handleability, processability, strength, etc., the thickness of the substrate film is usually 5 μm to 300 μm, preferably 10 μm to 200 μm, and more preferably 10 μm to 50 μm.
[0138] Next, the solvent is removed by drying, etc., thereby forming a dry coating. As a drying method, natural drying, ventilation drying, heating drying and reduced pressure drying methods can be cited. At this time, by heating the coating obtained by the composition for forming a liquid crystal curable film, the solvent can be dried and removed from the coating, and the polymerizable liquid crystal compound is oriented in the desired direction such as the horizontal direction relative to the plane of the coating. The heating temperature of the coating can be appropriately determined in consideration of the materials of the polymerizable liquid crystal compound used and the substrate film to be formed, etc., in order to make the polymerizable liquid crystal compound phase transition to a liquid crystal phase state, it is usually necessary to be a temperature above the liquid crystal phase transition temperature. In order to remove the solvent contained in the composition for forming a liquid crystal curable film while making the polymerizable liquid crystal compound a desired orientation state, for example, it can be heated to a temperature above the liquid crystal phase transition temperature (smectic phase transition temperature or nematic phase transition temperature) of the polymerizable liquid crystal compound contained in the composition for forming a liquid crystal curable film. The heating temperature is preferably a temperature higher than 3°C than the liquid crystal phase transition temperature of the polymerizable liquid crystal compound, and more preferably a temperature higher than 5°C than the liquid crystal phase transition temperature of the polymerizable liquid crystal compound. The upper limit of the heating temperature is not particularly limited, but is preferably 180° C. or lower, more preferably 150° C. or lower in order to avoid damage to the coating film, substrate film, etc. due to heating.
[0139] It should be noted that the liquid crystal phase transition temperature can be measured using, for example, a polarizing microscope, a differential scanning calorimeter (DSC), a thermogravimetric differential thermal analyzer (TG-DTA) and the like with a temperature regulating workbench. In addition, when two or more kinds are used in combination as polymerizable liquid crystal compounds, the above-mentioned phase transition temperature refers to: a mixture of polymerizable liquid crystal compounds obtained by mixing all polymerizable liquid crystal compounds constituting the composition for forming a liquid crystal curing film with the same ratio as the composition in the composition for forming a liquid crystal curing film, and the temperature measured in the same manner as the case of using one polymerizable liquid crystal compound. In addition, it is also known that the liquid crystal phase transition temperature of the polymerizable liquid crystal compound in the composition for forming a liquid crystal curing film is usually lower than the liquid crystal phase transition temperature of the polymerizable liquid crystal compound monomer.
[0140] The heating time can be appropriately determined depending on the heating temperature, the type of polymerizable liquid crystal compound used, the type of solvent, its boiling point and its amount, etc., and is usually 0.5 to 10 minutes, preferably 0.5 to 5 minutes.
[0141] The removal of the solvent from the coating film can be carried out simultaneously with the heating reaching the liquid crystal phase transition temperature or above of the polymerizable liquid crystal compound, or it can be carried out separately, but from the viewpoint of improving productivity, it is preferably carried out simultaneously. Before the heating reaching the liquid crystal phase transition temperature or above of the polymerizable liquid crystal compound, a pre-drying process for appropriately removing the solvent in the coating film under the condition that the polymerizable liquid crystal compound contained in the coating film obtained by the liquid crystal curable film forming composition will not polymerize can also be provided. As the drying method in the pre-drying process, natural drying method, ventilation drying method, heating drying method and reduced pressure drying method etc. can be cited.
[0142] Then, in the obtained dry coating, while maintaining the orientation state of the polymerizable liquid crystal compound, the polymerizable liquid crystal compound is polymerized by light irradiation, thereby forming a liquid crystal cured film as a polymer of the polymerizable liquid crystal compound in the desired orientation state. As a polymerization method, photopolymerization is generally used. In photopolymerization, the light irradiated to the dry coating can be appropriately selected according to the type of photopolymerization initiator contained in the dry coating, the type of polymerizable liquid crystal compound (especially the type of polymerizable group possessed by the polymerizable liquid crystal compound) and its amount. As a specific example, active energy rays such as light selected from the group consisting of visible light, ultraviolet light, infrared light, X-rays, α rays, β rays and γ rays, and active electron beams can be cited. Among them, from the aspect of easy control of the progress of the polymerization reaction, the device widely used in the art can be used as a photopolymerization device. It is preferred that ultraviolet light, preferably, the type of polymerizable liquid crystal compound and photopolymerization initiator is selected in advance in a manner that can be photopolymerized using ultraviolet light. In addition, during polymerization, it is also possible to utilize appropriate cooling means to cool the dry coating film while performing light irradiation, thereby controlling the polymerization temperature. If the polymerization of polymerizable liquid crystal compounds is implemented at a relatively low temperature by adopting such cooling means, even if a film with lower heat resistance is used as a substrate film, a liquid crystal cured film can be appropriately formed. In addition, it is also possible to promote the polymerization reaction by increasing the polymerization temperature within the range of not generating adverse conditions caused by the heat during light irradiation (deformation of the substrate film due to heat, etc.). During photopolymerization, it is also possible to obtain a patterned cured film by performing masking, development, etc.
[0143] As the light source of active energy rays, for example, there can be mentioned a low-pressure mercury lamp, a medium-pressure mercury lamp, a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a xenon lamp, a halogen lamp, a carbon arc lamp, a tungsten lamp, a gallium lamp, an excimer laser, an LED light source that emits light in a wavelength range of not less than 380 nm and not more than 440 nm, a chemical lamp, a black light lamp, a microwave-excited mercury lamp, a metal halide lamp, and the like.
[0144] The UV radiation intensity is usually 10mW / cm 2 Above 3,000mW / cm2 The ultraviolet irradiation intensity is preferably an intensity in a wavelength region effective for activating the photopolymerization initiator. The irradiation time is usually 0.1 second to 10 minutes, preferably 0.1 second to 5 minutes, more preferably 0.1 second to 3 minutes, and further preferably 0.1 second to 1 minute. When irradiating once or more times with such an ultraviolet irradiation intensity, the cumulative light amount is 10 mJ / cm 2 Above 3,000mJ / cm 2 Below, preferably 50mJ / cm 2 Above 2,000mJ / cm 2 Below, more preferably 100 mJ / cm 2 Above 1,000mJ / cm 2 the following.
[0145] The thickness of the optical anisotropic layer 30 (each layer in the case of comprising two or more liquid crystal cured films) is 0.1 μm or more and 5 μm or less, preferably 0.5 μm or more and 3 μm or less, more preferably 1.0 μm or more, further preferably 1.5 μm or more, and more preferably 2.5 μm or less. If the thickness of the liquid crystal cured film is within the above range, it is easy to present the prescribed optical properties and it is easy to improve the curvature of the optical laminate. The thickness of the liquid crystal cured film can be measured using an interference film thickness meter, a laser microscope or a stylus film thickness meter.
[0146] like Figure 1 The optical laminate of the present invention may include an orientation layer 60, as shown in the optical laminate 1. In this case, a liquid crystal cured film may be formed on the orientation layer 60. The orientation layer 60 has an orientation control force that orients the polymerizable liquid crystal compound in a desired direction. By forming a liquid crystal cured film using a horizontal orientation layer having an orientation control force that orients the polymerizable liquid crystal compound in a horizontal direction and a vertical orientation layer having an orientation control force that orients the polymerizable liquid crystal compound in a vertical direction, the polymerizable liquid crystal compound can be oriented in a desired direction with higher precision, and a liquid crystal cured film that exhibits excellent optical properties when assembled in an image display device or the like can be obtained. The orientation control force can be arbitrarily adjusted by the type of the orientation layer, the surface state, the friction conditions, etc., and when the orientation layer is formed of a photo-orientable polymer, it can be arbitrarily adjusted by polarized light irradiation conditions, etc.
[0147] The state of liquid crystal orientation, such as horizontal orientation, vertical orientation, mixed orientation, and tilted orientation, varies according to the properties of the orientation layer 60 and the polymerizable liquid crystal compound, and their combination can be selected arbitrarily. For example, when the orientation layer 60 is a material that serves as an orientation control force to make it present a horizontal orientation, the polymerizable liquid crystal compound can form a horizontal orientation or a mixed orientation, and when it is a material that makes it present a vertical orientation, the polymerizable liquid crystal compound can form a vertical orientation or a tilted orientation. Expressions such as horizontal and vertical indicate the direction of the long axis of the polymerizable liquid crystal compound that has been oriented with the plane (main surface) of the optically anisotropic layer 30 as a reference. For example, the so-called vertical orientation refers to the long axis of the polymerizable liquid crystal compound that has been oriented in a direction perpendicular to the plane (main surface) of the optically anisotropic layer 30. The so-called vertical here means 90°±20° relative to the plane (main surface) of the optically anisotropic layer 30.
[0148] As the orientation layer, it is preferred that the layer has solvent resistance that does not dissolve due to the application of the composition for forming a liquid crystal curable film, and has heat resistance in the heating treatment for removing the solvent and orienting the polymerizable liquid crystal compound. As the orientation layer, there can be cited an orientation film containing an oriented polymer, a photo-alignment film, a groove orientation film having a concave-convex pattern and a plurality of grooves on the surface, a stretched film stretched along the orientation direction, etc. From the viewpoint of the accuracy and quality of the orientation angle, the photo-alignment film is preferred.
[0149] As the oriented polymer, for example, polyamides having amide bonds in the molecule, gelatins, polyimides having imide bonds in the molecule and polyamic acid, polyvinyl alcohol, alkyl-modified polyvinyl alcohol, polyacrylamide, polyoxazole, polyethyleneimine, polystyrene, polyvinyl pyrrolidone, polyacrylic acid and polyacrylates can be cited. Among them, polyvinyl alcohol is preferred. The oriented polymer can be used alone or in combination of two or more.
[0150] The oriented film containing the oriented polymer can be obtained by applying a composition obtained by dissolving the oriented polymer in a solvent (hereinafter, also referred to as "oriented polymer composition") to the surface of the substrate film or the like to form an oriented layer, removing the solvent, or applying the oriented polymer composition to the substrate, removing the solvent and rubbing (rubbing method). As the solvent, the same solvent as the solvent exemplified above as the solvent that can be used in the composition for forming a liquid crystal cured film can be cited.
[0151] The concentration of the oriented polymer in the oriented polymer composition is preferably 0.1% to 20% by mass, more preferably 0.1% to 10% by mass, calculated as solid content relative to the solution, as long as the oriented polymer material can be completely dissolved in the solvent.
[0152] As a method for applying the oriented polymer composition to the surface of the substrate film or the like where the oriented layer is to be formed, the same method as the method exemplified as the method for applying the composition for forming a liquid crystal cured film to the substrate film can be cited. As a method for removing the solvent contained in the oriented polymer composition, natural drying method, ventilation drying method, heating drying method and reduced pressure drying method can be cited.
[0153] In order to impart an orientation control force to the orientation layer, a rubbing treatment (rubbing method) may be performed as required. As a method for imparting an orientation control force using the rubbing method, the following method may be cited: a film of an oriented polymer formed on the surface of a substrate film by coating an oriented polymer composition on a substrate film and annealing the film is brought into contact with a rubbing roller wound with a rubbing cloth and rotating. During the rubbing treatment, if masking is performed, multiple regions (patterns) with different orientation directions may also be formed on the orientation layer.
[0154] The photo-alignment film can be obtained by applying a composition comprising a polymer having a photoreactive group (photo-alignment polymer) and / or a monomer having a photoreactive group (photo-alignment monomer) and a solvent (hereinafter, also referred to as a "photo-alignment film-forming composition") to the surface of the substrate film to be formed into the alignment layer, removing the solvent, and irradiating with polarized light (preferably polarized UV light). The photo-alignment film is also advantageous in that the direction of the alignment control force can be arbitrarily controlled by selecting the polarization direction of the irradiated polarized light.
[0155] The so-called photoreactive group refers to a group that generates liquid crystal orientation ability by light irradiation. Specifically, groups that participate in the photoreactions that are the origin of the liquid crystal orientation ability, such as the orientation induction or isomerization reaction, dimerization reaction, photocrosslinking reaction or photodecomposition reaction of molecules that occur by light irradiation, can be cited. Among them, the group participating in the dimerization reaction or the photocrosslinking reaction is preferred from the aspect of excellent orientation. As a photoreactive group, it is preferably a group having an unsaturated bond, especially a double bond, and it is particularly preferred to have at least one group selected from the group consisting of a carbon-carbon double bond (C=C bond), a carbon-nitrogen double bond (C=N bond), a nitrogen-nitrogen double bond (N=N bond) and a carbon-oxygen double bond (C=O bond).
[0156] As photoreactive groups having C=C bonds, vinyl, polyene, stilbene, stilbazolyl, stilbazolinium, chalcone and cinnamoyl groups can be cited. From the perspective of easy control of reactivity and orientation control during photo-orientation, chalcone and cinnamoyl groups are preferred. As photoreactive groups having C=N bonds, groups having structures such as aromatic Schiff bases and aromatic hydrazones can be cited. As photoreactive groups having N=N bonds, azophenyl, azonaphthyl, aromatic heterocyclic azo, disazo, formazan and groups having an oxidized azobenzene structure can be cited. As photoreactive groups having C=O bonds, benzophenone, coumarin, anthraquinone and maleimide groups can be cited. These groups can have substituents such as alkyl, alkoxy, aryl, allyloxy, cyano, alkoxycarbonyl, hydroxyl, sulfonic acid, and halogenated alkyl.
[0157] Furthermore, the polymer having a photoreactive group may have an adhesive group on its side chain in order to obtain adhesiveness with the base film or the optically anisotropic layer 30. Examples of the adhesive group include an epoxy group, an oxetane group, and a (meth)acryloyl group.
[0158] The solvent contained in the photo-alignment film-forming composition may be the same solvents as those exemplified above as the solvents that can be used in the liquid crystal cured film-forming composition, and may be appropriately selected according to the solubility of the photo-alignment polymer or photo-alignment monomer having a photoreactive group.
[0159] The content of the polymer or monomer having a photoreactive group in the composition for forming a photo-alignment film can be appropriately adjusted according to the type of the polymer or monomer and the thickness of the target photo-alignment film, and is preferably at least 0.2% by mass, more preferably in the range of 0.3% by mass to 10% by mass, relative to the mass of the composition for forming a photo-alignment film. The composition for forming a photo-alignment film can contain a polymer material such as polyvinyl alcohol and polyimide, and a photosensitizer within a range that does not significantly impair the properties of the photo-alignment film.
[0160] As a method for applying the composition for forming a photo-alignment film on the surface of a substrate film or the like where an alignment layer is to be formed, the same method as the method for applying the alignment polymer composition can be cited. As a method for removing the solvent from the applied composition for forming a photo-alignment film, for example, natural drying, ventilation drying, heating drying, and reduced pressure drying can be cited.
[0161] In order to irradiate polarized light, it can be a form of directly irradiating polarized UV light to the product obtained by removing the solvent from the composition for forming a light-aligned film applied to the substrate film, or it can be a form of irradiating polarized light from the substrate film side, so that the polarized light is transmitted and irradiated. In addition, the polarized light is preferably substantially parallel light. The wavelength of the polarized light irradiated is preferably a wavelength in the wavelength region where the photo-reactive group of the photo-aligned polymer or photo-aligned monomer with a photo-reactive group can absorb light energy. Specifically, it is preferably UV (ultraviolet light) in the range of more than 250nm and less than 400nm in wavelength. As the light source used in the polarized light irradiation, ultraviolet lasers such as xenon lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, KrF, ArF, etc. can be cited, preferably high-pressure mercury lamps, ultra-high-pressure mercury lamps and metal halide lamps. These lamps are preferably due to the large luminous intensity of ultraviolet light with a wavelength of 313nm. The light from the aforementioned light source can be irradiated through an appropriate polarizer, thereby irradiating polarized UV light. As the polarizer, a polarizing filter, a polarizing prism such as Glan-Thompson or Glan-Taylor, or a wire grid type polarizer can be used.
[0162] The groove oriented film is a film having a concavo-convex pattern or a plurality of grooves (grooves) on the film surface. When a polymerizable liquid crystal compound is applied to a film having a plurality of linear grooves arranged at equal intervals, the liquid crystal molecules are oriented in the direction along the grooves.
[0163] As methods for obtaining a grooved orientation film, there are: a method of exposing the surface of a photosensitive polyimide film through an exposure mask having a slit in a pattern shape, and then developing and rinsing to form a concave-convex pattern; a method of forming a layer of a pre-cured UV-curable resin on a plate-like original plate having grooves on its surface, and then transferring the formed resin layer to a substrate, etc. and curing it; and a method of pressing a roll-like original plate having a plurality of grooves against a film of a pre-cured UV-curable resin formed on the surface of the orientation layer to be formed to form concave-convex, and then curing it; and the like.
[0164] The thickness of the orientation layer 60 (an orientation film or a photo-orientation film including an oriented polymer) is usually 10 nm to 10,000 nm, preferably 10 nm to 2,500 nm, more preferably 10 nm to 1,000 nm, further preferably 10 nm to 500 nm, and particularly preferably 50 nm to 250 nm.
[0165] (5) First Adhesive Layer and Second Adhesive Layer
[0166] The transparent protective film 10 and the polarizer 20 are laminated via the first adhesive layer 51, and only the first adhesive layer 51 is sandwiched between the transparent protective film 10 and the polarizer 20. In addition, the polarizer 20 and the optically anisotropic layer 30 are laminated via the second adhesive layer 52, and only the second adhesive layer 52 is sandwiched between the polarizer 20 and the optically anisotropic layer 30. When the transparent protective film 10 and the polarizer 20 are laminated using the first adhesive layer 51, and the polarizer 20 and the optically anisotropic layer 30 are laminated using the second adhesive layer 52, it helps to improve the bendability of the optical laminate, thereby, even if it is repeatedly bent, it is possible to prevent defects such as peeling and cracking from occurring at the bent portion. Furthermore, since the transparent protective film 10 and the polarizer 20 are bonded together by the first adhesive layer 51 and the polarizer 20 and the optically anisotropic layer 30 are bonded together by the second adhesive layer 52 , an optical laminate having good adhesion between these layers can be formed.
[0167] The first adhesive layer 51 and the second adhesive layer 52 can be formed using an adhesive. As the adhesive that can form the adhesive layer, for example, a dry curing adhesive such as a water-based adhesive and a chemical reaction adhesive such as an active energy ray curing adhesive can be cited. The first adhesive layer 51 and the second adhesive layer 52 can be formed of different adhesives, but are preferably formed of the same adhesive.
[0168] As the dry curing type adhesive, for example, a polymer containing a monomer having a protic functional group such as a hydroxyl group, a carboxyl group or an amino group and an ethylenically unsaturated group, or a polyurethane resin as a main component, and a composition containing a crosslinking agent or a curing compound such as a polyaldehyde, an epoxy compound, a melamine compound, a zirconium oxide compound or a zinc compound, etc. As the polymer of a monomer having a protic functional group such as a hydroxyl group, a carboxyl group or an amino group and an ethylenically unsaturated group, ethylene-maleic acid copolymer, itaconic acid copolymer, acrylic acid copolymer, acrylamide copolymer, saponification of polyvinyl acetate, and polyvinyl alcohol resin, etc. are mentioned. Polyvinyl alcohol resin is preferred.
[0169] Examples of the polyvinyl alcohol-based resin include polyvinyl alcohol, partially saponified polyvinyl alcohol, completely saponified polyvinyl alcohol, carboxyl-modified polyvinyl alcohol, acetoacetyl-modified polyvinyl alcohol, hydroxymethyl-modified polyvinyl alcohol, and amino-modified polyvinyl alcohol. The content of the polyvinyl alcohol-based resin in the aqueous drying-curing adhesive is usually 1 part by mass or more and 10 parts by mass or less, preferably 1 part by mass or more and 5 parts by mass or less, relative to 100 parts by mass of water.
[0170] As polyurethane resins, polyester ionomer polyurethane resins and the like can be cited. The polyester ionomer polyurethane resins referred to herein are polyurethane resins having a polyester skeleton and a resin obtained by introducing a small amount of ionic components (hydrophilic components) therein. The ionomer polyurethane resins are emulsified in water without using an emulsifier to form an emulsion, so that they can be made into a water-based dry curing adhesive. When using polyester ionomer polyurethane resins, it is effective to use a water-soluble epoxy compound as a crosslinking agent.
[0171] As epoxy compounds, polyamide epoxy resins obtained by reacting polyamide polyamine (which is obtained by reacting polyalkylene polyamines such as diethylenetriamine or triethylenetetramine with dicarboxylic acids such as adipic acid) with epichlorohydrin, etc. can be cited. As commercial products of the polyamide epoxy resins, "Sumirez resin (registered trademark) 650" and "Sumirez resin (registered trademark) 675" (the above are made by Sumika Chemtex Co., Ltd.), "WS-525" (made by Japan PMC Co., Ltd.), etc. can be cited. When epoxy compounds are used, the amount added is usually 1 part by mass or more and 100 parts by mass or less, preferably 1 part by mass or more and 50 parts by mass or less, relative to 100 parts by mass of polyvinyl alcohol resin.
[0172] Among them, the drying-hardening adhesive is preferably an aqueous drying-hardening adhesive containing a polyvinyl alcohol-based resin.
[0173] The drying-curing adhesive may contain a solvent. Examples of the solvent include water, a mixed solvent of water and a hydrophilic organic solvent (for example, an alcohol solvent, an ether solvent, an ester solvent, etc.), and an organic solvent.
[0174] An active energy ray-curable adhesive as a chemical reaction adhesive refers to an adhesive that is cured by irradiation with active energy rays. The active energy ray-curable adhesive may contain a solvent. Examples of active energy ray-curable adhesives include: a cationically polymerizable adhesive containing an epoxy compound and a cationic polymerization initiator; a radically polymerizable adhesive containing a (meth)acrylic curing component and a radical polymerization initiator; an adhesive containing both a cationically polymerizable curing component such as an epoxy compound and a radically polymerizable curing component such as a (meth)acrylic compound, and also containing a cationic polymerization initiator and a radical polymerization initiator; and an adhesive that does not contain these polymerization initiators and is cured by irradiation with an electron beam; and the like.
[0175] Among them, as the active energy ray curing adhesive, preferably a free radical polymerizable active energy ray curing adhesive containing a (meth) acrylic acid curing component and a free radical polymerization initiator, and a cationic polymerizable active energy ray curing adhesive containing an epoxy compound and a cationic polymerization initiator. As the (meth) acrylic acid curing component, (meth) acrylic acid esters such as methyl (meth) acrylate and hydroxyethyl (meth) acrylate and (meth) acrylic acid can be mentioned. The active energy ray curing adhesive containing an epoxy compound can also contain polymerizable compounds other than the epoxy compound. As polymerizable compounds other than the epoxy compound, oxetane compounds, acrylic compounds, etc. can be mentioned.
[0176] As a free radical polymerization initiator, a photopolymerization initiator described above as a free radical polymerization initiator that can be incorporated into a composition for forming a liquid crystal curing film for forming a liquid crystal curing film can be cited. As a commercially available cationic polymerization initiator, "KAYARAD" (registered trademark) series (manufactured by Nippon Kayaku Co., Ltd.), "Cyracure UVI" series (manufactured by Dow Chemical), "CPI" series (manufactured by San-Apro Co., Ltd.), "TAZ", "BBI" and "DTS" (manufactured by Midori Kagaku Co., Ltd.), "ADEKA OPTOMER" series (manufactured by ADEKA Co., Ltd.), "RHODORSIL" (registered trademark) (manufactured by Rhodia Co., Ltd.), etc. can be cited. Relative to 100 parts by mass of the active energy ray-curable adhesive, the content of the free radical polymerization initiator and the cationic polymerization initiator is usually 0.5 parts by mass or more and 20 parts by mass or less, preferably 1 part by mass or more and 15 parts by mass or less.
[0177] When the first adhesive layer 51 is used for laminating the transparent protective film 10 and the polarizer 20, and the second adhesive layer 52 is used for laminating the polarizer 20 and the optical anisotropic layer 30, it is advantageous in terms of the bending and thinning of the optical laminate compared to the case of using an adhesive layer. From the viewpoint of improving the adhesion between the polarizer 20 and the optical anisotropic layer 30, the second adhesive layer 52 is preferably a layer formed by an active energy ray-curable adhesive, more preferably a layer formed by a free radical polymerizable active energy ray-curable adhesive, and further preferably a layer formed by a free radical polymerizable active energy ray-curable adhesive containing a (meth) acrylic curing component and a free radical polymerization initiator. The same is true for the first adhesive layer 51.
[0178] The thickness of the first adhesive layer 51 and the second adhesive layer 52 is preferably 10 nm or more, more preferably 30 nm or more, further preferably 50 nm or more, preferably 5000 nm or less, more preferably 3000 nm or less, and further preferably 2000 nm or less. If the thickness of the adhesive layer, especially the second adhesive layer 52, is within the above range, it is easy to improve the bending property of the optical laminate, thereby making it difficult to produce undesirable conditions such as peeling and cracking at the bent portion even if it is repeatedly bent. The thickness of the first adhesive layer 51 and the second adhesive layer 52 may be the same or different from each other.
[0179] The thickness of the adhesive layer can be measured using, for example, an interference film thickness meter, a laser microscope, or a stylus film thickness meter.
[0180] (6) Adhesive layer
[0181] The optical laminate has an adhesive layer 40 disposed on the side opposite to the polarizer 20 side in the optical anisotropic layer 30. The adhesive layer 40 can constitute one of the two main surfaces of the optical laminate. The adhesive layer 40 can be laminated on the surface opposite to the viewing side (transparent protective film 10 side) of the optical laminate, and can be used for bonding the optical laminate to an image display element such as an organic EL display element.
[0182] The thickness of the adhesive layer 40 may be, for example, 150 μm or less, preferably 100 μm or less, more preferably 50 μm or less, and further preferably 40 μm or less from the viewpoint of thinning. From the viewpoint of durability, the thickness of the adhesive layer 40 is usually 1 μm or more, preferably 5 μm or more, and more preferably 10 μm or more.
[0183] The adhesive layer 40 may be composed of an adhesive composition having (meth) acrylic resin, rubber resin, urethane resin, ester resin, silicone resin, or polyvinyl ether resin as a main component. Among them, an adhesive composition having (meth) acrylic resin as a base polymer having excellent transparency, weather resistance, heat resistance, etc. is preferred. The adhesive composition may also be an active energy ray curable type or a thermosetting type.
[0184] As the (meth) acrylic resin (base polymer) used in the adhesive composition, a polymer or copolymer using one or more of (meth) acrylic acid esters such as butyl (meth) acrylate, ethyl (meth) acrylate, isooctyl (meth) acrylate, 2-ethylhexyl (meth) acrylate as monomers can be preferably used. In the base polymer, it is preferred to copolymerize polar monomers. As polar monomers, monomers having carboxyl groups, hydroxyl groups, amide groups, amino groups, epoxy groups, etc., such as (meth) acrylic acid, 2-hydroxypropyl (meth) acrylate, hydroxyethyl (meth) acrylate, (meth) acrylamide, N,N-dimethylaminoethyl (meth) acrylate, and glycidyl (meth) acrylate can be cited.
[0185] The adhesive composition may be a composition containing only the above-mentioned base polymer, but usually further contains a crosslinking agent. As the crosslinking agent, metal ions that can form carboxylic acid metal salts with carboxyl groups as divalent or higher metal ions, polyamine compounds that can form amide bonds with carboxyl groups, polyepoxide compounds or polyols that can form ester bonds with carboxyl groups, and polyisocyanate compounds that can form amide bonds with carboxyl groups can be cited. Among them, polyisocyanate compounds are preferred.
[0186] <Method for producing an optical laminate>
[0187] The present invention also relates to a method for producing the optical layered body according to the present invention. The method for producing the optical layered body according to the present invention includes the following steps.
[0188] a phase difference film preparation step of preparing a laminated body including an optical anisotropic layer, an orientation layer and a substrate film in this order (hereinafter, the laminated body is also referred to as a "phase difference film");
[0189] A first bonding step of bonding the transparent protective film to the polarizer using a first adhesive;
[0190] A second bonding step of bonding the polarizer to the optically anisotropic layer of the phase difference film using a second adhesive;
[0191] A peeling step of peeling and removing the substrate film, or the substrate film and the orientation layer, from the laminate obtained by the second lamination step;
[0192] In the adhesive layer laminating step, an adhesive layer is laminated on the surface exposed in the peeling step.
[0193] In the retardation film preparation step, a retardation film may be produced. In this case, the method of forming the alignment layer and the optically anisotropic layer on the base film is as described above.
[0194] The first adhesive used in the first lamination step is an adhesive for forming the first adhesive layer, and the details of the adhesive are as described above. The first adhesive is preferably an active energy ray-curable adhesive, more preferably a free radical polymerizable active energy ray-curable adhesive, and further preferably a free radical polymerizable active energy ray-curable adhesive containing a (meth) acrylic curing component and a free radical polymerization initiator.
[0195] In the case where the first adhesive is a drying and curing adhesive, after the transparent protective film and the polarizer are laminated (laminated) via the first adhesive, the solvent in the first adhesive is dried and removed from the obtained laminate, and cured as appropriate. The drying process and / or solvent removal can be carried out, for example, by blowing hot air, and the temperature is usually 30°C to 200°C, preferably 35°C to 150°C, more preferably 40°C to 100°C, and further preferably 50°C to 100°C.
[0196] The drying and removal (curing as needed) of the solvent in the first adhesive is preferably performed together with the drying and removal (curing as needed) of the solvent in the second adhesive after the second bonding step of bonding (laminating) the polarizer and the retardation film via the second adhesive.
[0197] When the first adhesive is an active energy ray-curable adhesive, the first adhesive is cured by irradiating the active energy ray, thereby obtaining the first adhesive layer. The light source of the active energy ray is not particularly limited, and is preferably an active energy ray having a luminescence distribution below a wavelength of 400 nm, and more preferably ultraviolet rays. Specifically, low-pressure mercury lamps, medium-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, chemical lamps, black light lamps, microwave-excited mercury lamps, and metal halide lamps can be cited as light sources.
[0198] The light irradiation intensity for the active energy ray-curable adhesive can be appropriately determined according to the composition of the active energy ray-curable adhesive and is not particularly limited. The irradiation intensity in the wavelength region effective for activating the polymerization initiator is generally 10 mW / cm 2 Above 3,000mW / cm 2 The light irradiation time for the active energy ray-curable adhesive can be appropriately selected according to the active energy ray-curable adhesive to be cured, and is not particularly limited. It is usually 0.1 seconds to 10 minutes, preferably 1 second to 5 minutes, more preferably 5 seconds to 3 minutes, and even more preferably 10 seconds to 1 minute. When irradiated once or multiple times with such ultraviolet irradiation intensity, the cumulative light amount is usually 10mJ / cm 2 Above 3,000mJ / cm 2Below, preferably 50mJ / cm 2 Over 2,000mJ / cm 2 Below, more preferably 100 mJ / cm 2 Above 1,000mJ / cm 2 the following.
[0199] The curing of the first adhesive by irradiation with active energy rays is preferably performed together with the curing of the second adhesive after the second bonding step of bonding (laminating) the polarizer and the retardation film via the second adhesive.
[0200] The second laminating process can be performed in the same manner as the first laminating process. In one embodiment, the first laminating process and the second laminating process are performed simultaneously. The second adhesive is an adhesive that forms the second adhesive layer, and the details of the adhesive are as described above. The second adhesive is preferably an active energy ray-curable adhesive, more preferably a free radical polymerizable active energy ray-curable adhesive, and further preferably a free radical polymerizable active energy ray-curable adhesive containing a (meth) acrylic curing component and a free radical polymerization initiator. The first adhesive and the second adhesive can be different adhesives from each other, but are preferably the same adhesive.
[0201] Through the first lamination step and the second lamination step, a laminate having a layer structure of a transparent protective film / a first adhesive / a polarizer / a second adhesive / a phase difference film is obtained. For the laminate, before the peeling step, the solvent of the first adhesive and the second adhesive is dried, removed (cured as appropriate), or cured by irradiation with active energy rays.
[0202] When the first adhesive and the second adhesive are active energy ray-curable adhesives and the first adhesive and the second adhesive contained in the laminate are cured by irradiation with active energy rays, in one embodiment, the active energy rays are irradiated from the phase difference film side. This embodiment is advantageous because it can fully cure the first adhesive and the second adhesive even when the transparent protective film has ultraviolet absorption capacity, such as when the transparent protective film contains an ultraviolet absorber.
[0203] The above-mentioned laminated body in which the solvent of the first adhesive and the second adhesive is dried, removed (cured as the case may be), or cured by irradiation with active energy rays is subjected to a peeling step, and the base film, or the base film and the orientation layer are peeled off and removed, and the adhesive layer is laminated on the surface exposed by the peeling step, thereby obtaining an optical laminated body. When the base film is peeled off and removed in the peeling step, the following can be obtained: Figure 1 The optical laminate including the alignment layer 60 shown in FIG. 1 can obtain the following structure when the base film and the alignment layer are removed in the peeling step. Figure 2The optical stack shown does not contain an orientation layer 60 .
[0204] The optical laminate can be continuously manufactured by a roll-to-roll method. For example, the optical laminate can be continuously manufactured by the following method: a phase difference film wound into a roll is prepared, the phase difference film is unwound while being transported, an adhesive for bonding each layer is used, and a polarizer and a transparent protective film prepared separately are sequentially stacked on the phase difference film, and the adhesive is dried or cured, and then the substrate film, or the substrate film and the orientation layer are peeled off and removed, and an adhesive layer is stacked on the surface exposed by peeling. Therefore, in one embodiment, the optical laminate can be in the form of an optical laminate roll wound into a roll.
[0205] In one embodiment, the optical layered body is preferably laminated so that the angle between the slow axis (optical axis) of the optically anisotropic layer constituting the optical layered body and the absorption axis of the polarizer is 45±5°.
[0206] <Image Display Device>
[0207] The optical laminate of the present invention can be used for an image display device. The so-called image display device is a device having an image display element, including a light-emitting element or a light-emitting device as a light source. As an image display device, a liquid crystal display device, an organic electroluminescent (EL) display device, an inorganic electroluminescent (EL) display device, a touch panel display device, an electron emission display device (such as a field emission display device (FED), a surface field emission display device (SED)), an electronic paper (a display device using electronic ink and an electrophoretic element), a plasma display device, a projection type display device (such as a grating light valve (GLV) display device, a display device with a digital micromirror device (DMD)) and a piezoelectric ceramic display, etc. The liquid crystal display device can be any display device in a transmissive liquid crystal display device, a semi-transmissive liquid crystal display device, a reflective liquid crystal display device, a direct-view liquid crystal display device and a projection type liquid crystal display device. These display devices can be display devices that display two-dimensional images, or they can be stereoscopic display devices that display three-dimensional images. In particular, the optical laminate of the present invention can be suitably used for an organic electroluminescent (EL) display device, an inorganic electroluminescent (EL) display device, a liquid crystal display device, and a touch panel display device.
[0208] The optical layered body of the present invention has excellent bendability, and therefore, the image display device is preferably a flexible image display device. The flexible image display device preferably further includes a window and a touch sensor.
[0209] The flexible image display device is formed, for example, by a laminate for a flexible image display device and an organic EL display panel, and the laminate for a flexible image display device is arranged on the viewing side relative to the organic EL display panel, and is configured in a bendable manner. As a laminate for a flexible image display device, in addition to the optical laminate of the present invention, a window, a touch sensor, etc. may also be included. The order of stacking them is arbitrary, but it is preferred to stack them in the order of a window, an optical laminate, and a touch sensor from the viewing side, or in the order of a window, a touch sensor, and an elliptically polarizing plate.
[0210] If there is an optical laminate on the viewing side of the touch sensor, the pattern of the touch sensor becomes less visually recognizable, and the visual recognizability of the displayed image becomes better, so it is preferred. Each component can be laminated using an adhesive, a bonding agent, etc. In addition, the laminate for a flexible image display device can have a light-shielding pattern formed on at least one side of any layer of the window, the optical laminate, and the touch sensor.
[0211] The window is usually arranged on the viewing side of the flexible image display device, and is responsible for protecting other components from external impact or environmental changes such as temperature and humidity. The window is formed by a flexible transparent substrate and may include a hard coating on at least one side. There is no particular limitation on the window, touch sensor, etc. that constitute the laminate for the flexible image display device, and conventionally known items can be used.
[0212] Example
[0213] The present invention will be described in more detail below with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples. Unless otherwise specified, "%" and "part" in Examples refer to mass % and mass part, respectively.
[0214] <Example 1>
[0215] [Preparation of Photo-Alignment Film-Forming Composition (X)]
[0216] A photo-alignment material having the following structure (weight average molecular weight: 50,000, m:n=50:50) was prepared according to the method described in Japanese Patent Application Laid-Open No. 2021-196514. 2 parts of the photo-alignment material was mixed with 98 parts of cyclopentanone (solvent), and the resulting mixture was stirred at 80° C. for 1 hour to prepare a photo-alignment film-forming composition (X).
[0217] Photo-oriented materials:
[0218] [Chemical formula 3]
[0219]
[0220] [Production of polymerizable liquid crystal compound]
[0221] A polymerizable liquid crystal compound (A1) and a polymerizable liquid crystal compound (A2) having the structures shown below were prepared respectively. The polymerizable liquid crystal compound (A1) was prepared by the same operation as the method described in Japanese Patent Publication No. 2019-003177. The polymerizable liquid crystal compound (A2) was prepared by the same operation as the method described in Japanese Patent Publication No. 2009-173893.
[0222] Polymerizable liquid crystal compound (A1):
[0223] [Chemical formula 4]
[0224]
[0225] Polymerizable liquid crystal compound (A2):
[0226] [Chemical formula 5]
[0227]
[0228] 1 mg of polymerizable liquid crystal compound (A1) was dissolved in 10 mL of chloroform to obtain a solution. The obtained solution was placed in a measuring cuvette with an optical path length of 1 cm as a measuring sample, and the measuring sample was placed in an ultraviolet visible spectrophotometer ("UV-2450" manufactured by Shimadzu Corporation) to measure the absorption spectrum. The wavelength of maximum absorbance was read from the obtained absorption spectrum, and the maximum absorption wavelength λmax in the range of 300 to 400 nm was 356 nm.
[0229] [Preparation of Liquid Crystal Cured Film-Forming Composition (Y)]
[0230] The polymerizable liquid crystal compound (A1) and the polymerizable liquid crystal compound (A2) are mixed in a mass ratio of 90:10 to obtain a mixture. 0.1 parts of a leveling agent "BYK-361N" (manufactured by BM Chemie) and 3 parts of "Irgacure OXE-03" (manufactured by BASF Japan Co., Ltd.) as a photopolymerization initiator are added to 100 parts of the obtained mixture. Furthermore, N-methyl-2-pyrrolidone (NMP) is added in such a way that the solid content concentration becomes 13%. The mixture is stirred for 1 hour at a temperature of 80°C to prepare a composition (Y) for forming a liquid crystal curable film. The composition (excluding the solvent) of the composition (Y) for forming a liquid crystal curable film is shown in Table 1.
[0231] [Table 1]
[0232]
[0233] [Production of Phase Difference Film (Z)]
[0234] The composition (X) for forming a photo-alignment film was applied on a biaxially stretched polyethylene terephthalate (PET) film (manufactured by Diafoil Mitsubishi Resins Co., Ltd.) as a substrate film using a rod coater. The obtained coating film was dried at 120°C for 2 minutes and then cooled to room temperature to form a dry film. Then, a UV irradiation device (SPOT CURE SP-9; manufactured by USHIO INC.) was used to irradiate 100 mJ of polarized ultraviolet light (based on 313 nm) to obtain a photo-alignment film D. The thickness of the photo-alignment film D measured using an ellipsometer (ellipsometer) M-220 manufactured by JASCO Corporation was 200 nm.
[0235] The above-mentioned composition for forming a liquid crystal curable film was applied to the obtained photo-alignment film using a bar coater to form a coating film. The coating film was heated and dried at 120°C for 2 minutes and then cooled to room temperature to obtain a dry film. Next, a high-pressure mercury lamp ("Unicure VB-15201BY-A" manufactured by USHIO INC.) was used to irradiate the above-mentioned dry film under a nitrogen atmosphere at an exposure dose of 500 mJ / cm 2 The optical anisotropic layer was formed by curing the polymerizable liquid crystal compound in a state where the polymerizable liquid crystal compound was oriented in a horizontal direction relative to the substrate surface, and a phase difference film (Z) composed of a substrate film / photo-aligned film / optically anisotropic layer (horizontally aligned liquid crystal cured film) was obtained. The thickness of the optical anisotropic layer measured using a laser microscope LEXT OLS4100 manufactured by Olympus Corporation was 2.0 μm.
[0236] The liquid crystal side of the phase difference film (Z) was subjected to corona treatment, and the glass was bonded via a 25 μm thick pressure-sensitive adhesive manufactured by LINTEC, and the PET film was peeled off and removed. The in-plane phase difference value was measured using KOBRA-WR manufactured by Oji Instruments Co., Ltd. It should be noted that the in-plane phase difference value for light with wavelengths of 450 nm, 550 nm, and 650 nm was obtained using the Cauchy dispersion formula obtained from the measurement results of the in-plane phase difference value for light with wavelengths of 448.2 nm, 498.6 nm, 548.4 nm, 587.3 nm, 628.7 nm, and 748.6 nm.
[0237] As a result, in terms of the in-plane retardation values, Re(450)=122nm, Re(550)=140nm, Re(650)=144nm, and the relationship between the in-plane retardation values at each wavelength is as follows.
[0238] Re(450) / Re(550)=0.87
[0239] Re(650) / Re(550)=1.03
[0240] (Wherein, Re(450) represents the in-plane phase difference value for light with a wavelength of 450 nm, Re(550) represents the in-plane phase difference value for light with a wavelength of 550 nm, and Re(650) represents the in-plane phase difference value for light with a wavelength of 650 nm.)
[0241] [Production of polarizing film]
[0242] A polyvinyl alcohol film (PVA: average degree of polymerization of about 2400, degree of saponification of 99.9 mol % or more) with a thickness of 30 μm was uniaxially stretched to about 5 times by dry stretching, and then immersed in pure water at 40°C for 40 seconds while maintaining the tension. Then, it was immersed in a dyeing aqueous solution with a mass ratio of iodine / potassium iodide / water of 0.044 / 5.7 / 100 at 28°C for 30 seconds for dyeing. Next, it was immersed in a boric acid aqueous solution with a mass ratio of potassium iodide / boric acid / water of 11.0 / 6.2 / 100 at 70°C for 120 seconds. Then, after washing with pure water at 8°C for 15 seconds, it was dried at 60°C for 50 seconds while maintaining a tension of 300 N, and then dried at 75°C for 20 seconds to obtain a polarizer with a thickness of 12 μm in which iodine was adsorbed and oriented on the polyvinyl alcohol film.
[0243] [Production of optical laminate]
[0244] The phase difference film (Z), polarizer and saponified triacetyl cellulose film (TAC: Konica Minolta Opto (co., Ltd.) "KC4UY", thickness 40 μm) prepared above as a transparent protective film are stacked in this order, after corona treatment on the liquid crystal curing film side of the phase difference film, in a manner that the liquid crystal curing film side of the phase difference film is opposite to the polarizer, and in a manner that the side of the polarizer opposite to the phase difference film is opposite to the transparent protective film. At this time, an aqueous dry curing adhesive is injected between the liquid crystal curing film and the polarizer, and between the polarizer and the transparent protective film. In addition, they are stacked in a manner that the absorption axis of the polarizer is at an angle of 45° to the slow axis of the liquid crystal curing film in the phase difference film. The obtained laminate is passed through a clamping roller to bond the layers. While the tension of the obtained laminate is maintained at 430 N / m, it is dried at 60°C for 2 minutes. Then, only the base film (PET film) of the phase difference film was peeled off, and the adhesive layer with a separation film was laminated on the surface exposed by peeling, thereby obtaining an optical laminate (1) consisting of an adhesive layer with a separation film / photo-alignment film / optically anisotropic layer (liquid crystal cured film) / adhesive layer / polarizer / adhesive layer / transparent protective film. The thickness of the optical laminate (1) excluding the adhesive layer was 54 μm.
[0245] The aqueous dry-curable adhesive is prepared by adding 3 parts of carboxyl-modified polyvinyl alcohol (Kuraray Poval KL318; manufactured by Kuraray Co., Ltd.) and 1.5 parts of water-soluble polyamide epoxy resin (Sumirez resin 650; manufactured by Sumika Chemtex Co., Ltd., an aqueous solution with a solid content concentration of 30%) to 100 parts of water.
[0246] [Evaluation of optical laminate]
[0247] (1) Bendability evaluation
[0248] In the evaluation of the bendability, a bending tester ("CFT-720C" (trade name) manufactured by Covotech) is used to bend the optical laminate (1) in such a way that the transparent protective film side becomes the inner side to conduct the test. The adhesive layer side of the optical laminate (1) from which the separation film has been peeled off is bonded to the sample stage of the bending tester in a flat state (unbent state). When the optical laminate (1) is bent, the optical laminate is bent 180° in such a way that the distance between the opposing transparent protective films becomes 4.0 mm (bending radius R = 2 mm). Then, it is restored to its original flat state. When a series of operations are performed once, the number of bendings is counted as 1, and the bending operation is repeated. The bending speed is set to 60 rpm. The number of bendings when cracks occur in the area bent due to the bending operation and the adhesive layer floats is recorded as the limit bending number. The limit bending number is evaluated according to the following criteria.
[0249] A: Even after bending 100,000 times, there was no cracking or floating.
[0250] B: Cracks and lifting occur when the bending frequency is more than 80,000 times and less than 100,000 times
[0251] C: Cracks and lifting occur when the bending frequency is 50,000 or more and less than 80,000 times
[0252] D: Cracks and lifting occur when the bending frequency is 10,000 or more and less than 50,000 times.
[0253] E: Cracks and floating occur when the number of bends is less than 10,000 times
[0254] (2) Adhesion evaluation
[0255] Before forming an adhesive layer on the photo-alignment film of the optical laminate (1), a sample piece was cut out from an arbitrary position, and the adhesion between the optical anisotropic layer and the polarizer was evaluated according to the cross-cut test of JIS K 5600. The specific evaluation criteria are as follows. The results are shown in Table 2. The adhesion between the optical anisotropic layer of the optical laminate (1) and the polarizer was B.
[0256] A: No squares are peeled off
[0257] B: The coating film is partially peeled off (1% or more and less than 50%)
[0258] C: The entire coating surface peels off (more than 50%)
[0259] <Example 2>
[0260] The results are shown in Table 2, except that a corona-treated polymethyl methacrylate resin film (PMMA: manufactured by Sumitomo Chemical Co., Ltd., thickness 40 μm) was used as the transparent protective film, an optical layered body (2) was prepared and evaluated in the same manner as in Example 1.
[0261] <Example 3>
[0262] An optical layered body (3) was prepared and evaluated in the same manner as in Example 1 except that a corona-treated cyclic polyolefin resin film (COP: ZF-14 manufactured by Zeon Japan, thickness 40 μm) was used as the transparent protective film.
[0263] <Example 4>
[0264] An optical layered body (4) was prepared and evaluated in the same manner as in Example 1 except that a corona-treated polyethylene terephthalate film (PET: Diafoil, manufactured by Mitsubishi Plastics Co., Ltd., thickness: 38 μm) was used as the transparent protective film.
[0265] <Example 5>
[0266] The phase difference film (Z), polarizer and saponified triacetyl cellulose film (TAC: Konica Minolta Opto (Strain) "KC4UY") as a transparent protective film are stacked in this order, after the liquid crystal curing film side of the phase difference film is corona treated, in a manner that the liquid crystal curing film side of the phase difference film is opposite to the polarizer, and in a manner that the side of the polarizer opposite to the phase difference film is opposite to the transparent protective film. At this time, a free radical polymerizable ultraviolet curing adhesive is injected between the liquid crystal curing film and the polarizer, and between the polarizer and the transparent protective film. In addition, they are stacked in a manner that the absorption axis of the polarizer is at an angle of 45° to the slow axis of the liquid crystal curing film in the phase difference film. The obtained laminate is passed through a clamping roller to bond the layers. Ultraviolet light with an exposure amount of 1000mJ is irradiated from the phase difference film side of the obtained laminate. Then, only the base film (PET film) of the phase difference film was peeled off, and the adhesive layer with a separation film was laminated on the surface exposed by peeling, thereby obtaining an optical laminate (5) consisting of an adhesive layer with a separation film / photo-alignment film / optically anisotropic layer (liquid crystal cured film) / adhesive layer / polarizer / adhesive layer / transparent protective film. The thickness of the optical laminate (5) excluding the adhesive layer was 56 μm.
[0267] The radical polymerizable ultraviolet curing adhesive is prepared by mixing the following components, and is an ultraviolet curing adhesive containing a (meth)acrylic curing component and a radical polymerization initiator.
[0268] Acryloylmorpholine (produced by Kojin Co., Ltd.) 23.1 parts
[0269] Isostearyl acrylate (produced by Osaka Organic Chemical Industry) 31.1 parts
[0270] LIGHT ACRYLATE LA: Lauryl acrylate (made by Kyoei Chemical) 7.7 parts
[0271] PLACCEL FA1DDM: 23.1 parts of unsaturated fatty acid hydroxyalkyl ester-modified ε-caprolactone (manufactured by Daicel)
[0272] LIGHT ACRYLATE 1,9NDA: 1,9-nonanediol diacrylate (produced by Kyoei Chemical) 15.0 parts
[0273] ARUFON-UP1190: 15.3 parts of acrylic polymer (produced by Toa Gosei)
[0274] IRGCURE.907: 3.5 parts of 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one (manufactured by BASF)
[0275] KAYACURE DETX-S: 3.5 parts of diethylthioxanthone (made by Nippon Kayaku)
[0276] <Example 6>
[0277] The results are shown in Table 2, except that a corona-treated polymethyl methacrylate resin film (PMMA: manufactured by Sumitomo Chemical Co., Ltd., thickness 40 μm) was used as the transparent protective film, an optical layered body (6) was prepared in the same manner as in Example 5 and evaluated.
[0278] <Example 7>
[0279] An optical layered body (7) was prepared and evaluated in the same manner as in Example 5 except that a corona-treated cyclic polyolefin resin film (COP: ZF-14 manufactured by Zeon Japan, thickness 40 μm) was used as the transparent protective film.
[0280] <Example 8>
[0281] An optical layered body (8) was prepared and evaluated in the same manner as in Example 5 except that a corona-treated polyethylene terephthalate film (PET: Diafoil, manufactured by Mitsubishi Plastics Co., Ltd., thickness: 38 μm) was used as the transparent protective film.
[0282] <Example 9>
[0283] The phase difference film (Z), polarizer and saponified triacetyl cellulose film (TAC: Konica Minolta Opto (Strain) "KC4UY") as a transparent protective film are stacked in this order, after the liquid crystal curing film side of the phase difference film is corona treated, so that the liquid crystal curing film side of the phase difference film is opposite to the polarizer, and the side of the polarizer opposite to the phase difference film is opposite to the transparent protective film. At this time, a cationic polymerizable ultraviolet curing adhesive is injected between the liquid crystal curing film and the polarizer, and between the polarizer and the transparent protective film. In addition, they are stacked in a manner that the absorption axis of the polarizer is at an angle of 45° to the slow axis of the liquid crystal curing film in the phase difference film. The obtained laminate is passed through a clamping roller to bond the layers. While the tension of the obtained laminate is maintained at 430N / m, ultraviolet light with an exposure amount of 1000mJ is irradiated from the optical anisotropic layer side. Then, only the base film (PET film) of the phase difference film was peeled off, and the adhesive layer with a separation film was laminated on the surface exposed by peeling, thereby obtaining an optical laminate (9) consisting of an adhesive layer with a separation film / photo-alignment film / optically anisotropic layer (liquid crystal cured film) / adhesive layer / polarizer / adhesive layer / transparent protective film. The thickness of the optical laminate (9) excluding the adhesive layer was 55 μm.
[0284] The cationic polymerizable ultraviolet curing adhesive is a ultraviolet curing adhesive prepared by mixing the following components and containing an epoxy compound and a cationic polymerization initiator.
[0285] 3,4-Epoxycyclohexylmethyl 3,4-Epoxycyclohexanecarboxylate 40 parts
[0286] 60 parts of diglycidyl ether of bisphenol A
[0287] 4 parts of diphenyl (4-phenylthiophenyl) sulfonium hexafluoroantimonate (photocationic polymerization initiator)
[0289] <Example 10>
[0290] The optical layered body (10) was prepared and evaluated in the same manner as in Example 9 except that a corona-treated polymethyl methacrylate resin film (PMMA: manufactured by Sumitomo Chemical Co., Ltd., thickness 40 μm) was used as the transparent protective film.
[0291] <Example 11>
[0292] An optical layered body (11) was prepared and evaluated in the same manner as in Example 9 except that a corona-treated cyclic polyolefin resin film (COP: ZF-14 manufactured by Zeon Japan, thickness 40 μm) was used as the transparent protective film.
[0293] <Example 12>
[0294] An optical layered body (12) was prepared and evaluated in the same manner as in Example 9 except that a corona-treated polyethylene terephthalate film (PET: Diafoil, manufactured by Mitsubishi Plastics Co., Ltd., thickness: 38 μm) was used as the transparent protective film.
[0295] <Comparative Example 1>
[0296] An adhesive layer with a separation film is laminated on the substrate film surface of the laminate prepared according to Example 2 of Japanese Patent Publication No. 2022-044293 to obtain an optical laminate (13). The layer structure of the optical laminate (13) is adhesive layer with a separation film / substrate film / photo-alignment film / optically anisotropic layer (liquid crystal cured film) / adhesive layer / polarizer / adhesive layer / transparent protective film.
[0297] <Comparative Example 2>
[0298] An adhesive layer with a separation film is laminated on the surface of the optically anisotropic layer (liquid crystal cured film) of the laminate prepared according to Example 1 of Japanese Patent Application Publication No. 2022-044293 to obtain an optical laminate (14). The layer structure of the optical laminate (14) is adhesive layer with a separation film / optically anisotropic layer (liquid crystal cured film) / photo-alignment film / base film / adhesive layer / polarizer / adhesive layer / transparent protective film.
[0299] <Comparative Example 3>
[0300] An adhesive layer with a separation film is laminated on the substrate film surface of the laminate prepared according to Example 3 of Japanese Patent Publication No. 2022-044293 to obtain an optical laminate (15). The layer structure of the optical laminate (15) is adhesive layer with a separation film / substrate film / photo-alignment film / optically anisotropic layer (liquid crystal cured film) / adhesive layer / polarizer / adhesive layer / transparent protective film.
[0301] <Comparative Example 4>
[0302] An adhesive layer with a separation film is laminated on the substrate film surface of the laminate prepared according to Example 4 of Japanese Patent Application Publication No. 2022-044293 to obtain an optical laminate (16). The layer structure of the optical laminate (16) is adhesive layer with a separation film / substrate film / photo-alignment film / optically anisotropic layer (liquid crystal cured film) / adhesive layer / polarizer / adhesive layer / transparent protective film.
[0303] <Comparative Example 5>
[0304] An adhesive layer with a separation film is laminated on the photo-alignment film surface of a laminate prepared according to Comparative Example 1 of Japanese Patent Application Publication No. 2022-044293 to obtain an optical laminate (17). The layer structure of the optical laminate (17) is adhesive layer with a separation film / photo-alignment film / optically anisotropic layer (liquid crystal cured film) / adhesive layer / polarizer / adhesive layer / transparent protective film.
[0305] [Table 2]
[0306]
[0307] Description of Reference Numerals
[0308] 1, 2 optical laminate, 10 transparent protective film, 20 polarizer, 30 optically anisotropic layer, 40 adhesive layer, 51 first adhesive layer, 52 second adhesive layer, 60 orientation layer.
Claims
1. An optical laminate comprising, in order, a transparent protective film, a first adhesive layer, a polarizer, a second adhesive layer, an optically anisotropic layer and a pressure-sensitive adhesive layer, Only the first adhesive layer is sandwiched between the transparent protective film and the polarizer, and only the second adhesive layer is sandwiched between the polarizer and the optically anisotropic layer. The optically anisotropic layer is a liquid crystal cured film, The optically anisotropic layer has a thickness of 0.1 μm to 5 μm. The optically anisotropic layer is directly in contact with the pressure-sensitive adhesive layer, or an alignment layer is included between the optically anisotropic layer and the pressure-sensitive adhesive layer.
2. The optical laminate according to claim 1, wherein: The thickness of the first adhesive layer and the second adhesive layer is not less than 50 nm and not more than 2000 nm.
3. The optical laminate according to claim 1, wherein: The first adhesive layer and the second adhesive layer are layers formed of a dry-curable adhesive or an active energy ray-curable adhesive.
4. The optical laminate according to claim 1, wherein: The optically anisotropic layer has reverse wavelength dispersion.
5. The optical laminate according to claim 1, wherein: The in-plane retardation value of the optically anisotropic layer with respect to light of a wavelength of 550 nm is 100 nm or more and 160 nm or less.
6. The optical laminate according to claim 1, wherein: The optically anisotropic layer has an optical axis that is tilted with respect to the longitudinal direction of the polarizer.
7. The optical laminate according to claim 1, wherein: The alignment layer is a photo-alignment film formed of a photo-alignment polymer including a photo-reactive group.
8. The optical laminate according to claim 1, wherein: The transparent protective film further includes an anti-reflection layer on a side opposite to the polarizer.
9. The optical layered body according to claim 1, wherein: The polarizer is composed of a polyvinyl alcohol-based resin film containing a dichroic dye. 10 . An image display device comprising the optical layered body according to claim 1 .
11. The method for producing an optical layered body according to any one of claims 1 to 9, comprising the following steps: a retardation film preparation step of preparing a retardation film including an optical anisotropic layer, an orientation layer and a substrate film in sequence; A first bonding step of bonding the transparent protective film to the polarizer using a first adhesive; A second bonding step of bonding the polarizer to the optically anisotropic layer of the phase difference film using a second adhesive; A peeling step of peeling and removing the base film, or the base film and the alignment layer, from the laminate obtained by the second lamination step; and The adhesive layer laminating step is to laminate the adhesive layer on the surface exposed by the peeling step.
12. The method for producing an optical layered body according to claim 11, wherein: The first adhesive and the second adhesive are active energy ray-curable adhesives.
13. The method for manufacturing an optical layered body as described in claim 12, further comprising the following step: after the second bonding step and before the peeling step, irradiating the layered body obtained by the second bonding step with active energy rays from the phase difference film side to cure the first adhesive and the second adhesive.
Citation Information
Patent Citations
Compound, optical film, and manufacturing method for optical film
JP2009173893A
Polymerizable liquid crystal composition and retardation plate
JP2019003177A
Polarizing film, polarizing plate, optical laminate, elliptical polarizing plate, organic el display, and flexible image display device
JP2021196514A
Optical laminate and elliptically polarizing plate including the same
JP2022044293A